Investigation on the separation mechanism of Knelson concentrator ring-by-ring based on a relative concentration criterion - Qiao Chen; Yang Yang; Jinglin Han; Hongying Yang; Linlin Tong (Minerals Engineering, 2026)

Single-cell transcriptomics reveals cellular heterogeneity and cell–cell communication networks in free gossypol-induced enteritis in juvenile largemouth bass (Micropterus salmoides) - Xinpeng Wang; Wanying Jiang; Linlin Li; Jun Wen; Limeng Wang; Shimei Lin; Yongjun Chen; Li Luo; Xinghua Zhou; Yuanfa He (Fish & Shellfish Immunology, 2026)

SND1 regulates the androgen signaling axis by stabilizing EIF3B mRNA to facilitate the deterioration of prostate cancer - Ying Li; Chengru Yang; Guoli Cui; Shiliang Gui; Linlin Jia; Yu Chen; Honglin Niu; Hua Xin (Molecular Genetics and Genomics, 2026)

ARHI as a key regulator of EMT and metastasis in pancreatic cancer via the Notch-1 pathway - Jingjing Liu; Yiqun Zhao; Ying Wang; Ying Shi; Qiang Zhi; Linlin Chen; Yuhao Ke; Jianlin Ren (Human Genetics, 2026)

Assessing present-day tectonic stability, sea-level change, and tsunami hazards from a coastal multi-hazard GNSS station in the southern South China Sea - Qiang Qiu; Linlin Li; Mai Ye; Hongqiang Yang; Xingyu Song; Jian Ping Yin; Tingting Zheng; Jinghe Cao; Peitao Wang; Zhanying Chen; Zhiwen Zhang; Kuilin Xiao; et al. (Engineering Geology, 2026)

Synthesis and characterization of porous carbon from Hawaii nut shells for effective CO2 capture - Xiaohan Liu; Yingyi Wang; Zhentao Chen; Xin Hu; Qiang Xiao; Leihong Zhao; Muslum Demir; Murat Kilic; Mohammed K. Al Mesfer; Linlin Wang (Biomass and Bioenergy, 2026)

Interactions of Micro/Nanoplastics and Antibiotics: Research Trends, Toxicological Effects, and Environmental Risks - Junyi Du; Jia Du; Linlin Qiu; Qingwei Zhou; Meiqing Jin; Jianjun Chen; Weihong Wu (Water, Air, & Soil Pollution, 2026)

Artificial intelligence-driven food labels: Technological convergence, application innovation, and sustainable future - Linlin Zhao; Xingyu Chen; Wenqin Gu; Huinan Jiang; Bimal Chitrakar; Xiangren Meng (Trends in Food Science & Technology, 2026)

Characteristics of overpressure and thermal effects of methane–air explosions in tunnels - Linlin Gu; Zhenjing Nie; Yi Li; Zhen Wang; Chuyuan Huang; Xianfeng Chen (Fuel, 2026)

Plasma-based biomimetic antigen outpost synergizes with immune checkpoint blockade to enhance antitumor immunity via dual inhibition of SOCS1 and PD-L1 pathways in dendritic cells - Siyuan Meng; Fangnan Lv; Jieqing Chen; Linlin Tao; Hao Guo; Danhui Wang; Jie Sun; Jian Li; Ning Liu; Wei Xu; Meirong Huo (Chemical Engineering Journal, 2026)

The Ecosystem Health Assessment of the Intertidal Zone in the Yellow River Delta - Shaoyu Jiang; Baoquan Li; Jiao Wang; Jing Chen; Linlin Chen (Wetlands, 2026)

A novel Chaphamaparvovirus detected in breeding Muscovy Ducks with hepatitis - Yadong Gao; Jiawen Dong; Ouyang Peng; Zhuanqiang Yan; Meiting Chen; Yingshan Yin; Minhua Sun; Junqin Zhang; Yunzhen Huang; Yong Xiang; Zhai Qi; Junwei Ge; et al. (Veterinary Research Communications, 2026)

Optimal grasping direction of a flexible gripper and its RGB-D multimodal estimation method - Jingwei Sun; Linlin Sun; Shuangxi Liu; Huawei Yang; Zixu Chen; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Cerium oxide nanoparticles in agroecosystems: stage-dependent impacts on sorghum growth, forage quality, bioenergy composition, and environmental risk - Linlin Mu; Mahsa Ghorbani; Fatemeh Ganjalikhan Hakemi; Zohreh Ranjbar; Caroline Korte; Bradley Rauh; Gongde Chen; Haizhou Liu; William Bridges; Stephen Kresovich; Christophe J.G. Darnault (Total Environment Advances, 2026)

Arbuscular mycorrhizal fungi improve the mechanical properties of root–soil composites of different vegetation types in a loess subsidence area - Wenbo Zhu; Yinli Bi; Chao Wu; Linlin Xie; Zengming Ke; Jinduo Chen (Rhizosphere, 2026)

Organophosphate flame retardants and incident type 2 diabetes: Integrating population evidence, mechanistic insights, and effect modification by healthy lifestyle - Xueyan Wu; Yilin Zhou; Yue Nie; Haoran Xu; Hengrui Liu; Mengke Cheng; Yao Guo; Fangyuan Lin; Xin Tang; Peihan Chen; Dandan Wei; Jian Hou; et al. (Journal of Hazardous Materials, 2026)

Glycated walnut protein linseed gum conjugates for HIPE-based dressing - Bin Zhang; Li Yang; Xia Chen; Ziyi Liao; Linlin Hou; Kai Zheng; Congfang Li; Juan Dong (Journal of Food Engineering, 2026)

Tackling antibiotic resistance genes as environmental contaminants: Innovations in advanced oxidation processes and strategic solutions - Chen Gao; Liang Zhang; Linlin Zang; Hian Kee Lee; Sheng Tang (Journal of Environmental Sciences, 2026)

Unique coordination of four-metal-atom clusters on C5N2H2 boosts nitrogen reduction reaction performance: a DFT study - Linlin Li; Shaopeng Xu; Yan Yan; Mengmeng Wang; Yan Chen; Jiaojiao Chen; Wei Li; Xunlei Ding (Fuel, 2026)

Rural domestic waste generation characteristics and treatment-related greenhouse gas emissions: A case study of Guangdong Province, China - Yao He; Jie Zhang; Chen Lin; Linlin Xia; Yazhuo Wang; Hewen Zhou; Xun-an Ning (Environmental Pollution, 2026)

A dual-modified NASICON cathode achieving 15,000 cycles and wide-temperature operation (−20 to 55 °C) for practical sodium-ion batteries - Linying Yuan; Yuping Liao; Bing Han; Tianchen Shen; Kai Wang; Luyang Chen; Shigang Lu; Linlin Wang (Chemical Engineering Journal, 2026)

Spatial heterogeneity of ice phenology in large lakes of Xinjiang, China - Kangzheng Zhong; Jiaxin Hao; Puzhe Huo; Chunpeng Chen; Linlin Cui; Liping Xu; Zhijun Li; Jiang Li; Guanghui Wei (Regional Environmental Change, 2026)

VHGAE: Drug-Target Interaction Prediction Model Based on Heterogeneous Graph Variational Autoencoder - Chen Zhang; Jiaqi Sun; Linlin Xing; Longbo Zhang; Hongzhen Cai; Kai Che (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Antibiotics and antibiotic resistance genes increase cyanobacterial blooms by altering microbial nitrogen transformations in water and sediment - Linlin Zhu; Tao Huang; Bo Wang; Lijun Zhou; Qingye Sun; Kaining Chen (Water Research, 2026)

Cellulose sulfate-modified biochar loaded with Rs-2 for improving saline-alkali soil - Linlin Zhu; Yao Chen; Nana Liu; Yanhui He; Xiaochen Liu; Qiuyu Chen; Fei Tian; Zhansheng Wu (Soil and Tillage Research, 2026)

Activating Na4 site via crystalline-phase-engineering enables charge redistribution and stress mitigation in Na4Fe3(PO4)2P2O7 cathodes - Linlin Zhou; Danjing Yang; Shuting Wen; Ling Chen; Chenwei Li; Haifeng Yu; Hao Jiang; Chunzhong Li (Science Bulletin, 2026)

Biodegradable piezoelectric suture for real-time biomechanical sensing and therapeutic intervention - Quanhong Hu; Chuyu Tang; Zhirong Liu; Shaobo Wang; Zhuo Wang; Genglin Chen; Shuncheng Yao; Zhuoheng Jiang; Songjing Zhong; Yuxuan Zhang; Linlin Li (Science Bulletin, 2026)

Synergistic enhancement of heavy rare earth elements leaching from ion-adsorption rare earth ores using fungal metabolites supplemented with ammonium sulfate - Yun Fang; Hailan Wang; Linlin Yan; Jianxiong Zeng; Siqi Chen; Jun Liu; Guowei Wang; Yang Liu; Jun Wang; Chunqiao Xiao (Hydrometallurgy, 2026)

Ambient-temperature hydrogen storage kinetics of magnesium-based composites enabled by acetone-assisted ball milling and TiF3 catalysis - Linlin Zhang; Qingyun Shi; Chunmin Zhang; Bingbing Chen; Chunli Wang; Limin Wang; Yong Cheng (Fuel, 2026)

Effect of coupled temperature-humidity drying on multi-scale structure and in vitro digestibility of corn resistant starch - Qing Su; Lirong Chen; Linlin Sun; Xingya Wang; Yuqiu Guo; Meimei Zhao; Kaichang Liu; Kuijie Gong (Food Chemistry, 2026)

Transforming waste derived phosphate sources into resources for fluoride immobilization by microbially induced phosphate precipitation - Linlin Cui; Jianxing Sun; Min Huang; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Bioresource Technology, 2026)

Exploring Co-occurrence Patterns of Macrobenthic Communities Across Intertidal and Offshore Zones in the Yellow River Delta, China - Jiao Wang; Shaoyu Jiang; Debin Sun; Jing Chen; Baoquan Li; Linlin Chen (Wetlands, 2026)

Role of M1 macrophage-derived exosomes in infantile hemangioma regression via AMPK/SIRT1/PGC1α pathway - LinLin Yue; XiuWen Zheng; XiaoQiang Wen; Yong Zeng; Wei Peng; QianDuo Li; LinShan Zeng; JinPing Liu; Yu Wang; WenQing Fu; HaiJin Liu; Feng Chen (Molecular & Cellular Toxicology, 2026)

Benthic Fauna of Foraminifera and Their Distribution Pattern in Sishili Bay, Northern Yellow Sea, China - Tatyana S. Tarasova; Baoquan Li; Yulia A. Trebukhova; Ilia A. Shcherbakov; Aleksandra V. Romanova; Konstantin A. Lutaenko; Jiao Wang; Jing Chen; Linlin Chen (Journal of Ocean University of China, 2026)

Clinical and Molecular Characterization of Five Additional Individuals With SATB2-Associated Syndrome in Guangxi - Sheng Yi; Qinle Zhang; Fei Chen; Xunzhao Zhou; Qiang Zhang; Shang Yi; Xiaofei Zhang; Jiale Qian; Linlin Wang; Shujie Zhang; Biyan Chen; Zailong Qin; et al. (Biochemical Genetics, 2026)

Microbiological safety of dehydrated foods: risk analysis, technology evaluation, and synergistic strategies for next-generation processing - Yu Wang; Wenchao Liu; Linlin Li; Weiwei Cao; Junliang Chen; Chung Lim Law; Guangyue Ren; Xu Duan (Critical Reviews in Food Science and Nutrition, 2026)

5-FU chemotherapy induces functional CD7+ and IL7R+ CTLs infiltration to suppress colorectal tumor progression - Yanmin Wu; Yan Li; Xufeng Yao; Yiyang Pan; Linlin Chen; Jian Zhang; Boyu Luo; Yue Teng; Mingqing Zhang; Chunwan Lu (Science China Life Sciences, 2026)

Prescription principle, phytochemistry, pharmacological activities and clinical applications of Huangqin decoction: a comprehensive review - Yan Fang; Haizhen Liang; Linlin Lu; Xijie Tian; Yuting Zhang; Junyu Zhang; Zhifeng Dai; Xiaojuan Chen; Juan Song; Tao Su; Zhongqiu Liu; Baiping Ma (Phytochemistry Reviews, 2026)

Breakage mitigation optimization strategy for a spiral-groove wheel fertilizer distributor based on a controlled-release fertilizer breakage model - Hongjian Zhang; Xiubo Chen; Xinpeng Cao; Yongxian Wang; Xin Han; Junshuo Xu; Linlin Sun; Jing Wang; Linlong Jing; Jinxing Wang (Computers and Electronics in Agriculture, 2026)

Co-adaptive dynamics of human activity and crop Climatic Niches in the Neolithic Wei River Valley, China (8000–4000 cal. BP) - Xiang Jinhui; Shao Bingxin; Zhou Mile; Wang Yanpeng; Zhai Linlin; Chen Honghai; Zhang Gaike; Ma Zhikun (Quaternary Science Reviews, 2026)

Source-sink dynamics of WADA-prohibited compounds in coastal urban aquatic environments: From WWTP to bay - Min Zhou; Zifan Weng; Linlin Zhang; Shen Yu; Bing Hong; Yuxin Chen; Zhixing Yang; Qian Sun; Tao Ma; Dunming Xu (Journal of Environmental Management, 2026)

Spatial heterogeneity of wildfires in Southern China during the Last Glacial Maximum - Binxu Liu; Jia Liu; Xingyuan Qin; Linlin Chen; Jiaxi Zhou; Zhiyun Lu; Robert A. Spicer; Shufeng Li; Tao Su (Global and Planetary Change, 2026)

A barnacle-inspired hydrogel enables external-internal synergistic modulation of NF-κB/Nrf2 signaling for diabetic wound healing - Xuetong Ji; Junyao Li; Xintao Gao; Jiqing Dong; Linlin Ma; Yu Han; Xiangyan Chen; Yantao Li (Chemical Engineering Journal, 2026)

Fabrication of aramid nanofiber/silver nanoparticles composite aerogels for enhanced electromagnetic interference shielding - Mingyan Wang; Linlin Cheng; Jinxiao Hou; Shaojuan Chen; Liang Jiang; Yanfen Zhou (Chemical Engineering Journal, 2026)

Extreme warming and pulsed volcanism during the Paleocene-Eocene Thermal Maximum - Abdelhamid M. Salman; Xue-Ting Wang; Zuoling Chen; Linlin Cui; Hongwei Li; Xu Wang (Science China Earth Sciences, 2026)

Sustained Swimming Training Enhances Growth and Swimming Performance in Juvenile Coho Salmon (Oncorhynchus kisutch) with Limited Effects on Osmoregulatory-Related Traits - Wenda Cui; Hexiang Yang; Shuang Song; Linlin Dai; Hongyang Chen; Junjie Bai; Binbin Xing; Xintong Qiu (Fishes, 2026)
To evaluate the effects of swimming training on growth, swimming performance, and osmoregulatory-related indices in juvenile coho salmon, freshwater-reared fish were subjected to current of 1 body length per second (BL·s−1) from December 2024 to April 2025. Fork length, body weight, condition factor, insulin-like growth factor-1 (IGF-1), and gill and intestinal Na+/K+-ATPase (NKA) protein abundance were measured monthly, and critical swimming speed (Ucrit) was evaluated after one month of training. Trained fish showed greater fork length in March and higher body weight in March and April than controls. The condition factor was higher in trained fish in February and March, but declined during spring smolt development. Swimming capacity was enhanced by training, as indicated by significantly higher Ucrit. Mean IGF-1 levels did not differ between groups, but IGF-1 correlated positively with body size only in trained fish. No significant training effect was detected for either gill or intestinal NKA protein abundance, although gill NKA increased significantly in April, likely reflecting seasonal smoltification. In addition, IGF-1 was significantly correlated with gill NKA in trained fish in March. Collectively, these results indicate that sustained swimming training improves growth and swimming performance and may enhance associations among measured physiological variables during smoltification in juvenile coho salmon.

Antibacterial and antioxidant activity of ginsenosides from ginseng rootlets and their application in beef preservation - Junshun Zhang; Maoyu Wang; Suwan Lu; Yuhui Zhi; Luchen Bi; Yuxian Wang; Linlin Yin; Yi Wang; Zhina Chen (World Journal of Microbiology and Biotechnology, 2026)

Mechanistic study of wheat straw-enhanced sulfur release and denitrification in a pyrite-based bioretention system: Iron–sulfur–carbon synergistic interactions - Zhaoyang You; Jinlong Wang; Tao Wang; Xi Chen; Yongmei Zhang; Su Li; Linlin Tong; Kinjal J. Shah (Chemosphere, 2026)

Distributed three-dimensional target enclosing control for AUVs under ocean currents - Linlin Shi; Haoming Wu; Biao Wei; Simin Lv; Yang Xu; Ronghao Zheng; Yu Chen (Ocean Engineering, 2026)

Fouling and retention behavior of micro- and nano-plastics in gravity-driven membrane filtration - Xueying Chen; Dongwei Lu; Tongyu Li; Qingcan Zhou; Yinkun Sun; Linlin Zang; Jun Ma (Journal of Water Process Engineering, 2026)

Nitrogen cycle suppression and enhanced carbon burial during the Paleocene-Eocene thermal maximum, recorded from Tarfa section, Egypt (Tethys Ocean) - Abdelhamid M. Salman; Xueting Wang; Zuoling Chen; Hongwei Li; Linlin Cui; Nageh A. Obaidalla; Xu Wang (Global and Planetary Change, 2026)

Mechanism of texture formation in dried fruits and vegetables: from macroscopic to the molecular level - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Food Control, 2026)

A first quantitative assessment of seabed litter collection efficiency using bottom otter trawls and fishery depletion models - Yue Chen; Xinxing You; Linlin Gao; Huaxiang Sheng; Yipu Sui; Xinle Xu; Liuyi Huang (Environmental Pollution, 2026)

Breaking the trade-off: A phosphorylated interpenetrating network bridging ion-conduction pathways for safe and high-performance solid-state batteries - Yuyang Wang; Linlin Wang; Jie Yang; Qiuya Wang; Junye Zhang; Cheng Liu; Zaichao Zhang; Le Xu; Rundong Chen; Tianchen Shen; Shigang Lu; Luyang Chen (Chemical Engineering Journal, 2026)

CTAB regulated front-end synthesis of schwertmannite for rapid high-capacity as(III) removal with structure evolution and mechanistic insights - Mingjun Zou; Yajing Chen; Linlin Tong; Hongying Yang (Chemical Engineering Journal, 2026)

Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Dose- and time-dependent cardioprotection of liproxstatin-1 via sequential modulation of ferroptosis pathways after myocardial ischemia-reperfusion - Ziwei Huang; Xixi Chen; Junyi Ren; Linlin Wan; Miao Li; Xiaowu Ma; Jing Dong; Hong Ran (Molecular and Cellular Biochemistry, 2026)

PCBs exposure and renal injury: comprehensive assessment strategy based upon TRAEC strategy - Zhiyuan Chen; Changqian Liu; Linlin Zhang; Jianrong Han; Xiaoyan Ding; Changshun Han; Sihao Zhu; Jiabao Cao; Jiaxin Song; Fucong Zhang; Jian Li; Zhenghong Zuo; et al. (Journal of Environmental Management, 2026)

Polyphenol oxidase-mediated browning during storage of Pinus elliottii oleoresin: characterization of pine-needle PPO and antibrowning action of L-cysteine - Siheng Zhang; Hanxiao Liu; Jingcong Liu; Lu Qin; Xin Li; Xuanrou Wei; Xiaopeng Chen; Linlin Wang (Food Bioscience, 2026)

Effects of combined selenium and sulfur application on glucosinolate biosynthesis in Chinese cabbage sprouts - Huixia Bai; Linlin Zhao; Yafang Luo; Qi Hu; Lingling Liu; Yang Chen; Huan Wang; Yushu Wang (Physiology and Molecular Biology of Plants, 2026)

Similarity-based classification of groundwater hydrographs to reveal regional groundwater dynamics patterns in a semi-arid agricultural area - Xiangbo Meng; Xi Chen; Yonggen Zhang; Man Gao; Linlin Lu (Hydrogeology Journal, 2026)

FAdV-4-induced secondary Pasteurella multocida infection potentiates bacterial adherence and aggravates pathological damage in SPF chickens - Yuxin Chen; Guizhen Yi; Yunzhen Huang; Linlin Li; Jiawen Dong; Yong Xiang; Minhua Sun; Junqin Zhang; Bin Wu (Veterinary Microbiology, 2026)

The role of microplastics in bioavailability and toxicity of triclosan in the soil-earthworm system: Inhibitor or facilitator - Xian Chen; Jingcheng Liang; Linlin Shi; Shipeng Luo; Rong Ji; Jiehong Cheng; Ying Wu; Yuchen Wang (Journal of Environmental Chemical Engineering, 2026)

Efficient hydrogenation of heavy turpentine into high-energy-density biofuel over MOF-derived nano-Ni@C/rGO and associated kinetic insights - Xiaoying Tang; Yongxiong Yang; Ying Tang; Shen Luo; Xiaopeng Chen; Xu Wei; Linlin Wang (Journal of Environmental Chemical Engineering, 2026)

Unlocking circularity in rural waste management in northwest China: A systematic framework to quantify energy-environment-pollution nexus - Yuansheng Huang; Linlin Wang; Yi Liu; Yihan Chen; Xinglin Zhang; Yiliang He (Journal of Cleaner Production, 2026)

Bioaugmentation of thiourea-acclimated biomass relieves thiourea’s inhibition of nitrification - Meng Huang; Xiaobing Gao; Ning Yan; Fei Liu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Journal of Environmental Chemical Engineering, 2026)

Association of prenatal exposure to polychlorinated biphenyls with cleft lip and/or palate risk in offspring: A case-control study - Sainan Li; Shujian Lin; Yongyan Chen; Yiqi Ding; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Environmental Sciences, 2026)

Insights into the mechanism of nutty aroma formation by Staphylococcus saprophyticus in fermented sausages - Jikun He; Youqin Duan; Shuting Yang; Fidel Toldrá; Jiong Zheng; Muying Du; Linlin Wang; Nodali Ndraha; Shuyao Wang; Juan Chen (International Journal of Food Microbiology, 2026)

Multifunctional nanoemulsion co-delivering Lactobacillus plantarum supernatant and Litsea cubeba essential oil: Construction and application in fiddlehead fern preservation - Jiayue Song; Dengyi Ye; Wenjia Li; Qiao Guo; Yanan Zhang; Xiyu Wang; Ping Tang; Ping Chen; Linlin Xu (Food Bioscience, 2026)

Edge-cloud collaborative digital twin for vibration anomaly detection and localization in high-rise buildings - Chen Xiong; Huijin Zhu; Jie Huang; Kuangyu Chen; Weizong Lai; Linlin Xie; Liu Mei (Engineering Structures, 2026)

Study on the Separation of Co(II) Ions by Triethylenetetramine-Modified Polyacrylonitrile Nanofibers - Yang Luo; Shuyuan Liu; Weiwei Li; Guangchuan He; Guangfu Chen; Xianchen Huang; Xiangyang Niu; Jiahui Ruan; Linlin Huang; Guoyuan Yuan (Water, Air, & Soil Pollution, 2026)

Proteostasis Collapse Drives Effector Memory T Cells Re-expressing CD45RA (TEMRA) Generation in the Tumor Microenvironment - Linlin Li; Shuo Kan; Qiang Huang; Shiwen Wang; Yuchen Han; Liang Chen; Jun Jin (Phenomics, 2026)

Leveraging butter-whey protein interactions to engineer starch-based inks for high-fidelity 3D food printing - Xinyu Wei; Limin Cheng; Wenchao Liu; Zhenbin Liu; Chaofan Guo; Linlin Li; Weiwei Cao; Xu Duan; Guangyue Ren; Weihua Guo; Wei Chen; Lifeng Pan (Journal of Food Engineering, 2026)

Pretreatment-driven shrinkage regulation in Chinese yam during multiphase microwave drying - Rongtian An; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Min Zhang; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Occurrence, composition profiles, and human exposure assessment of liquid crystal monomers in indoor dust from Wuxi, China - Yiyang Yao; Linlin Wu; Run Zhou; Xi Wang; Yan Gong; Rong Chen; Wenwei Liu (Environmental Pollution, 2026)

Electronic structure tuning of Mn-based high-entropy spinel boosts benzene catalytic oxidation - Jiarui Chen; Xiaotong Li; Junjie Feng; Linlin Deng; Mingtai Li; Baojuan Dou; Feng Bin (Chemical Engineering Journal, 2026)

Synergistic effects of crystal-facet on dehalogenation kinetics and poison tolerance of Pd-based electrocatalytic membranes for efficient removal of halogenated pollutants - Yinkun Sun; Dongwei Lu; Xianci Pan; Rongxin Zeng; Zhiyu Sun; Xueying Chen; Yumei Wang; Qingcan Zhou; Yichao Hu; Linlin Zang; Guanjin Liu; Jun Ma (Chemical Engineering Journal, 2026)

Holocene wildfire activity archived in East Asian marginal sea: Linkages to climate variability and human civilization - Linlin Chen; Yazhi Bai; Zhigang Guo; Weini Chong; Yuying Zhang; Jinming Bai; Yaru Liu; Haiyan Fang; Limin Hu (CATENA, 2026)

Deubiquitinases in liver diseases: from mechanisms to targeted therapy - Zhenge Zhang; Wanli Duan; Yixiang Wang; Peng Hao; Linlin Chen; Ziyi Hao; Ming He; Yingli Wu; Hao Luo (Science China Life Sciences, 2026)

An overview of GNSS for tsunami early warning: From lithosphere to ionosphere - Kejie Chen; Haishan Chai; Jiafeng Li; Guoguang Wei; Mingzhe Lyu; Wenfeng Cui; Chuang Shi; Linlin Li; Peitao Wang; Wei Lu; Jian Lin (Science China Earth Sciences, 2026)

Ecological niche shapes the composition and function of microbial communities in Astragalus membranaceus - Xiao Chen; Zhengyan Li; Yaogong Zhang; Chao Yao; Yuanshuai Yu; Feifei Ding; Jingyi Xu; Yuan Li; Linlin Dong; Guangfei Wei (Plant and Soil, 2026)

Paleolandslides, paleoshorelines and lacustrine sediment deformation structures in the midstream Tashkurgan River, Chinese Pamir and implications on regional seismic risk - Liao Liye; Zeng Qingli; Du Linlin; Du Changhong; Chen Xuan; Shang Yanjun; Zhou Yuanze (Bulletin of Engineering Geology and the Environment, 2026)

Tidal irrigation-based rice cultivation enhances coastal blue carbon and decreases GHG emissions in brackish mudflats - Lang Zhang; Linlin Li; Hualei Yang; Wenbang Tang; Ji Chen; Hongkai Zhou; Ying Huang; Xuechu Chen; Xiuzhen Li; Ming Luo; Xingyun Huang; Faming Wang; et al. (Agricultural and Forest Meteorology, 2026)

A Deep-Sea Multi-Sequence Sampling System Integrating In Situ Microbial Filtration with Rapid RNA Stabilization - Wei Bu; Yuan-Jie Chen; Jinhai Luo; Linlin Sun; Xiang Li; Xinyuan Gao; Yuanli Fang; Leisheng Tang; Jiaying Zhao; Jingchun Feng; Haocai Huang (Journal of Marine Science and Engineering, 2026)
Rapid depressurization and warming during recovery can trigger stress in deep-sea microbes and accelerate RNA degradation. We developed a remotely operated vehicle (ROV)-oriented multi-sequence microbial sampler for 2000 m sampling (20 MPa, 2 °C) that integrates in situ filtration with immediate RNAlater injection (an RNA stabilization reagent), collecting up to 12 samples per dive. A Dirichlet sampling–B-spline–SVM framework was used to optimize the cam profile of the sequence trigger for robust actuation under geometric constraints and realistic tolerances in both manufacturing and assembly. Relative to the baseline 3-4-5 motion law, the optimized design reduces nominal peak driving torque by ~18–20% and lowers the maximum torque under tolerance perturbations; tests show a further ~10–25% reduction using a SiC ball–ZrO2 block pair versus a MoS2-lubricated titanium pushrod–ZrO2 block pair. A Darcy–Forchheimer porous-media computational fluid dynamics (CFD) model predicts earlier clogging on the lower membrane and a fast-to-slow RNAlater displacement process; greater membrane resistance mismatch delays 95% displacement and increases RNAlater loss. Simulations and Rhodamine B tests suggest an RNAlater consumption of 0.9 L per parallel filter (one membrane per side), and 20 MPa chamber tests confirm stable operation and membrane retrieval.

Insights into low temperature adaptation in Epinephelus awoara through integrated genome and transcriptome analysis - Linna Wang; Shuai Chen; Zhentong Li; Yang Liu; Shihao Wang; Tangtang Ding; Fengfan Yang; Chunbai Zhang; Linlin Li; Wensheng Li; Qingbin Wang; Xia Zhao; et al. (Aquaculture, 2026)

Machine learning based prediction of mechanical properties in carbon fiber recovered through pyrolysis - Xiang Guo; Tian Li; Chunting Liu; Meng Zhang; Hao Li; Jinrui Li; Yihua Zhang; Chunmei Zeng; Shuwu Wei; Linlin Pei; Fang Liu; Da Chen (Waste Management, 2026)

From firm to soft: Maturity-driven mechanical damage behavior of apples - Zixu Chen; Linlong Jing; Ruofei Liu; Huawei Yang; Linlin Sun; Xinpeng Cao; Yongxian Wang; Shenghui Fu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2026)

Analysis of shrinkage deformation behavior in microwave vacuum drying of Chinese yam based on evolution of physical properties - Qian Zhou; Linlin Li; Lijuan Wang; Wenchao Liu; Weiwei Cao; Tongxiang Yang; Junliang Chen; Guangyue Ren; Chung Lim Law; Xu Duan (Journal of Food Engineering, 2026)

Adsorption mechanism of hydrogen bromide and 2-bromophenol on CuO, Cu2O, α-Fe2O3, and NiO catalysts: A density functional theory study - Lushi Sun; Jiaxing Du; Tao Chen; Gan Wan; Linlin Xu; Li Lin (Journal of Environmental Chemical Engineering, 2026)

The sequestration of metal nanoparticles in the liver: A trade-off between density and degradability - Junjie Ma; Li Zeng; Yaquan Liu; Shunhao Wang; Min Li; Linlin Yao; Gang Tang; Ziniu Wang; Jiexia Cheng; Qi Wu; Guangxuan Wang; Chunzhen Shi; et al. (Journal of Environmental Sciences, 2026)

Influence of pore fluid on the elasto-plastic property of shales - Linghao Chen; Wanqing Shen; Shuitao Zhang; Zhilei Luo; Jianfu Shao; Linlin Wang (International Journal of Rock Mechanics and Mining Sciences, 2026)

Meteorological observation research based on an improved EfficientNetV2 model - Haozheng Yin; Yu Cao; Linlin Liu; Dan Chen; Qiong Zhang (Environmental Modelling & Software, 2026)

Development and application of a numerical model of an asynchronized parallel double-stage fluid viscous damper for seismic responses control based on OpenSees - Linlin Xie; Haoxiang Wang; Cantian Yang; Aiqun Li; Yue Chen (Engineering Structures, 2026)

Black phosphorus quantum dots regulate inflammation and neural stem cells differentiation via Notch1 signaling through cell adhesion - Lu Chen; Yongyuan Guo; Lusen Shi; Shiji Zhang; Linlin Jiang; Yong Chang; Haoran Liu; Zihang Wang; Na Li; Shiqing Feng (Chemical Engineering Journal, 2026)

Hydrodynamics, mixing performance and power consumption in horizontal millimeter-scale helical tube reactors: comprehensive experimental and numerical investigations across a wide range of centrifugal-to-gravitational acceleration ratio - Zhongyao Zhang; Yuanjie Wu; Xiaopeng Chen; Jiezhen Liang; Qianyun Tan; Chenghong Wu; Bo Feng; Denghan Luo; Linlin Wang (Chemical Engineering Journal, 2026)

O2-supplementing photosensitizer AuNCs@TAT as a highly efficient NIR-II-controllable pyroptosis inducer for cancer photoimmunotherapy - Linlin Xie; Xingye Ma; Zheng Wang; Caifang Wang; Zhongxin Xiao; Ling-Dong Sun; Chun-Hua Yan; Chen-Jie Fang (Chemical Engineering Journal, 2026)

Numerical Simulation of Gas Production and Geomechanical Response of Heterogeneous Gas Hydrate Reservoirs - Jiuhui Cheng; Shuitao Zhang; Linlin Wang; Guangjin Chen (Natural Resources Research, 2026)

An integrated multiscale computational study of nephrotoxicity mechanism of citrinin and its metabolites (CIMs)：density functional theory, network toxicology, and molecular dynamics simulation - Jiaxing Li; Furong Xue; Linlin Xu; Huijing Zhang; Xizi Zhang; Chenchen Qi; Chengtao Wang; Wei Chen; Di Zhang (Mycotoxin Research, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Bone mesenchymal stem cells attenuate axonopathy in spinal cord of rats exposed to 2,5-hexanedione via NGF-dependent and -independent pathways - Qiufang Bai; Zhe Li; Jing Chen; Man Liu; Xiaodan Shao; Xiaochi Chen; Fengyuan Piao; Linlin Fang (Molecular and Cellular Biochemistry, 2026)

Drug screening reveals the mechanism of toyocamycin-induced apoptosis in triple-negative breast cancer organoids - Houshi Ma; Linlin Lu; Yuqing Tu; Xiaoran Chang; Huabin Jiang; Tianhang Yang; Shun Wang; Jinxian Wang; Jinbing Xue; Yan Chen; Gangyin Luo (Toxicology and Applied Pharmacology, 2026)

Involvement of ARTS in bisphenol A-induced apoptosis of mouse Leydig cells - Ying Yang; Si Yang; Meijuan Zhang; Linlin Xu; Jiaxiang Chen (Toxicology, 2026)

CsNAC73 promotes cold-induced theanine biosynthesis by activating CsAlaDC expression in albino Camellia sinensis cv. Baiye 1 - Dandan Li; Ying Sun; Xin He; Xin Cheng; Maoyin Fu; Xuchun Zhang; Qi Chen; Xiaochun Wan; Linlin Liu (Plant Science, 2026)

From association to mechanism: Prenatal PFAS Co-exposures induces fetal neural tube defects via autophagy-mediated ferroptosis - Yongyan Chen; Qianhui Cheng; Chen Yang; Sainan Li; Hai Lin; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2026)

Comparative metabolomic analysis of spray- and freeze-dried Cornus officinalis microcapsules reveals temperature-dependent flavonoid retention and optimal encapsulation conditions - Wenchao Liu; Xinyu Wei; Lijuan Wang; Linlin Li; Weiwei Cao; Yilin Huang; Junliang Chen; Chung Lim Law; Qing Sun; Guangyue Ren; Xu Duan (Innovative Food Science & Emerging Technologies, 2026)

Thermal performance assessment of coupled soil stratification and groundwater advection effects on vertical borehole heat exchanger - Linlin Zhang; Dongyang Fan; Yanbin Li; Tianhao Yuan; Jun Chen (Geothermics, 2026)

Inhalable tetrahedral DNA nanoplatforms for dual-barrier penetration and sustained deep-lung delivery of small-molecule drugs - Fenglin Jiang; Qi Han; Hao Deng; Jiaqi Li; Alimire Alifu; Zhuo Chen; Linlin Deng; Xiaoxiao Cai; Yu Chen; Yunfeng Lin (Chemical Engineering Journal, 2026)

Harnessing β-glucans for immune regulation: Bridging structural diversity, therapeutic potential, and functional food development - Xue Wang; Linlin Ma; Chen Chen; Lina Ma; Xian Qu; Ai Ren; Yifa Zhou; Hairong Cheng (Carbohydrate Polymers, 2026)

The Key Role of Somatostatin Neurons in the Suprachiasmatic Nucleus in Anxiety-Depression Comorbidity Following Sleep Deprivation - Yifei Zhang; Yuxin Wang; Xinyue Liu; Chunlin Ren; Ming Chen; Linlin Bi (Molecular Neurobiology, 2026)

HDC-Net: A hierarchical detection and counting framework for apple aphids with density-level classification - Bo Ma; Zhuo Ren; Shuangxi Liu; Linlin Sun; Junlin Mu; Qiaolin Chen; Jiawei Xu; Rongsen Xie; Xianliang Hu; Yongqiang Zheng; Hongjian Zhang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

An experimental study of the influence of local segment damage on dynamic response characteristics of shield tunnels - Linlin Yang; Wenbo Yang; Yang Zhou; Zefeng Chen; Chaofan Yao (Tunnelling and Underground Space Technology, 2025)

LARS1 knockdown suppresses the biological activities of thyroid cancer cells by stimulating autophagy - Congwen Jin; Chuanhong Li; Linlin Chen; Hao Liu; Yousheng Yu; Benxin Chen (Tissue and Cell, 2025)

Learning to reason over multi-granularity knowledge graph for zero-shot urban land-use mapping - Yansheng Li; Yu Wang; Lei Yu; Bo Dang; Gang Xu; Zhenyu Zhong; Yuning Wu; Xin Guo; Kang Wu; Zheng Li; Linlin Wang; Jian Wang; et al. (Remote Sensing of Environment, 2025)

A LiDAR-based approach for real-time bulk coal extraction in cargo holds - Xinyi Yu; Dachuan Shi; Yuanlong Li; Kuiguang Jiao; Changrui Chen; Linlin Ou (Ocean Engineering, 2025)

Delayed algal blooms to runoff surges in low-runoff estuaries: hydrodynamic and nutrient driving mechanisms and early warning strategies - Linlin Wang; Zuoyi Chen; Gang Wang; Yike He; Lin Mu; Xianzhong Mao; Hongsheng Bi; Jiabo Zhang (Journal of Hydrology, 2025)

Filamentous cyanobacterium Spirulina platensis mediates phosphate biomineralization for efficient fluoride immobilization and drives metabolic shift toward stress resistance and biomineralization - Linlin Cui; Zhilian Liu; Jun Suo; Yun Liu; Guanzhou Qiu; Zhu Chen; Hongbo Zhao; Li Shen (Journal of Hazardous Materials, 2025)

Electroenhanced organic pollutant adsorption by three - dimensional isolated electrodes: Investigation of the “short - plate effect” - Xinyu Wang; Xiaochen Zhang; Linlin Chen; Fei Yu; Jie Ma (Journal of Cleaner Production, 2025)

The gold, palladium, silver, copper, and silicon were synergistically recovered from the waste chips through the phase reconstruction and stepwise recovery methods - Shuo Liu; Yaobin Lai; Xin Chen; Jian Li; Hui Zhang; Linlin Chang; Tianyi Chen; Xuxia Zhang; Yangyang Xie; Liuyimei Yang; Tao Qi (Journal of Environmental Chemical Engineering, 2025)

Study on slow pyrolysis mechanism of non-metallic fractions in waste printed circuit boards using TG-FTIR-MS analysis - Lushi Sun; Gan Wan; Tao Chen; Jiaxing Du; Linlin Xu; Haitao Liu (Journal of Environmental Management, 2025)

Aminated lignin-modified polyethersulfone membranes with enhanced antifouling performance for oil-water separation - Linlin Liang; Meijiao Peng; Hui Xu; Zijun Wu; Baojie Liu; Chengrong Qin; Chen Liang; Caoxing Huang; Shuangquan Yao (Journal of Environmental Chemical Engineering, 2025)

Field study on the occurrence and risk assessment of haloacetamides in drinking water systems - Ying Yu; Ruya Chen; Linlin Pan; Baoyou Shi (Journal of Environmental Chemical Engineering, 2025)

Zein/eugenol electrospun mats on gelatin/laponite substrate for developing bilayer functional food packaging - Minmin Chen; Linlin Li; Wei Ji; Wensheng Lu; Xiaochao Tang; Suwei Jiang; Hualin Wang (Food Research International, 2025)

Tracking Browning mechanistic pathway of postharvest pine resin using comparative metabolomics - Xin Li; Junsheng Lu; Junmei Ye; Yibin Qin; Xiaopeng Chen; Jiezhen Liang; Linlin Wang (Food Chemistry, 2025)

Engineering yeast expression platforms: Advanced strategies for heterologous protein production and glycosylation modification - Hao Li; Taichi Chen; Zikun Zhang; Qiyi Jiang; Weigang Yuwen; Linlin Qu; Rongzhan Fu; Chenhui Zhu; Huan Lei; Daidi Fan (Chemical Engineering Journal, 2025)

Mitochondria-targeted nanoparticles with whole-course-repair efficacy in therapy of myocardial ischemia reperfusion injury - Xiya Wang; Hang Chen; Pingyuan Sun; Linlin Zhao; Renxiang Gui; Xu Wang; Emeli Chatterjee; Jiahong Xu; Jianle Chen; Xuerui Chen (Chemical Engineering Journal, 2025)

Construction of temperature-responsive helical carbon nanofibers-based composites toward switchable microwave absorption - Yudi Li; Linlin Zhao; Wei Feng; Rongling Zhang; Xialong Cai; Zhiyong Chen; Hanjun Wei; Xulin Yang; Pan Wang; Giulio Cerullo; Nabil Kadhim Taieh; Fanbin Meng; et al. (Chemical Engineering Journal, 2025)

CTAB-mediated in situ synthesis of schwertmannite for enhanced As(V) removal from arsenic-contaminated wastewater: performance and mechanistic insights - Mingjun Zou; Yajing Chen; Linlin Tong; Zhenan Jin; Hongying Yang (Chemical Engineering Journal, 2025)

Highly efficient amino-functionalized ionic liquid membrane contactor coupled system for low-concentration carbon dioxide absorption and desorption - Rui Chen; Jiayi Xu; Zhuoran Chen; Nuo Cheng; Jing Wu; Linlin Sun; Junjie Li (Bioresource Technology, 2025)

The Impact of Microplastics on the Dissemination, Persistence, and Ecotoxicological Effects of Antibiotic Resistance Genes in Terrestrial Ecosystems - Jia Du; Tingting Chen; Luxi Niu; Lanxue Zhi; Linlin Qiu; Qingwei Zhou; Meiqing Jin; Weihong Wu (Water, Air, & Soil Pollution, 2025)

Microwave-assisted modification for enhancing the slow-release performance of biochar-based fertilizer and application - Linlin Zhu; Bingzhe Su; Chen Guan; Yao Chen; Dongye Huang; Jiayao Zhou; Qiuyu Chen; Xiaochen Liu; Fei Tian; Zhansheng Wu (Journal of Soils and Sediments, 2025)

CUR-PDT induces ferroptosis of RA-FLS via the Nrf2/xCT/GPX4 pathway to inhibit proliferation in rheumatoid arthritis - Lihua Sun; Yajuan Niu; Bo Liao; Linlin Liu; Yi Peng; Kaiting Li; Xinhua Chen; Qing Chen; Dingqun Bai (Inflammation Research, 2025)

Cross-modal alignment and fusion of EEG-visual based on mixed attention mechanism for emotion recognition - Linlin Li; Wanzhong Chen (Cognitive Neurodynamics, 2025)

How do atmospheric pollutant changes driven by anthropogenic heat provide feedback on the urban thermal environment in Beijing? - Jiangkang Qian; Linlin Zhang; Xinran Zhu; Qingyan Meng; Xinli Hu; Jianfeng Gao; Shize Chen (Sustainable Cities and Society, 2025)

Multi-parameter input damage limit prediction for bare reinforced concrete frames using XGBoost - Chen Xiong; Yuchao Cao; Jingfeng Zheng; Linlin Xie; Liu Mei; Lixiao Li; Wujian Long (Soil Dynamics and Earthquake Engineering, 2025)

A highly sensitive and specific immunochromatographic test strip for detecting p,p′-DDA in seawater and shellfish - Teng Zhang; Yunrui Xing; Jiale Yao; Zhuan Yang; Jucai Wang; Linlin Chen; Lunguang Yao (Food Chemistry, 2025)

Investigating the aroma transition during rapid mango ripening driven by dynamic catabolism of fatty acids - Yuanping Wang; Zhenjiang Zhou; Yonghao Liu; Rongli Pang; Xi Zhao; Qi Chen; Linlin Guo; Baiyi Lu (Food Chemistry, 2025)

DHA sustains frozen-cell-induced efferocytosis by mitigating endoplasmic reticulum stress to promote inflammation resolution and bone repair - Boya Zhang; Hanze Du; Lei Huang; Lijun Liu; Jing Cui; Linlin Wen; Junguang Liu; Wenhao Zhai; Rongrong Ye; Yuhuan Li; Kexuan Liu; Wangni Xie; et al. (Chemical Engineering Journal, 2025)

Spin-polarization-enhanced photoreforming of plastic waste - Nan Zhou; Mai Zhang; Shiwei Lin; Linlin Zhang; Jianjun Liao; Chen Li; Wei Zhou (Chemical Engineering Journal, 2025)

Atmospheric and room temperature plasma mutagenesis of Graesiella emersonii for enhanced protein production using methanol as novel carbon source - Jixu Luo; Guanqin Huang; Mingjia Zheng; Changqing Ou; Qingyue Chen; Yufeng Ling; Linlin Cai; Yang Yang; Lingcheng Liu; Fei Huang; Zhangli Hu; Yihong Zheng (Bioresource Technology, 2025)

Biochar-induced strong microbial carbon limitation prompts organic carbon sequestration and plant growth in antibiotic-contaminated soil - Linlin Qiu; Tim J. Daniell; Muhammad Nafees; Yihao Chen; Shuyu Zhou; Weihong Wu; Jia Du; Qingwei Zhou; Meiqing Jin; Weiying Ji; Jiaying Ge; Hongyan Guo (Plant and Soil, 2025)

Salvianolic Acid B and Ginsenoside Rg1 Combination Attenuates Cerebral Edema Accompanying Glymphatic Modulation - Lingxiao Zhang; Yanan Shao; Zhao Fang; Siqi Chen; Yixuan Wang; Han Sha; Yuhan Zhang; Linlin Wang; Yi Jin; Hao Chen; Baohong Jiang (Neuroscience Bulletin, 2025)

An MA-film platform designed for high-throughput synthesis of calcium phosphates screening amino acid on collagen film - Xiaoyu Li; Xiran Yang; Xinkun Chen; Changxia Liu; Linlin Wu; Dazhuo Qiu; Xueye Chen; Xuetao Shi (Analytica Chimica Acta, 2025)

Proteomics and metabolic profiling of Vibrio parahaemolyticus at three different temperatures - Aiyun Meng; Zhigang Tu; Linlin Hu; Fuxiao Chen (Frontiers in Marine Science, 2025)
Introduction Microorganisms exist and survive in complex and variable environments. Bacteria communities response and adapt to the changing conditions. The Mechanisms underlying bacterial survival can be elucidated through the use of multi-omics techniques. Methods In this study, we test an approach for measuring how different temperatures (4°C, 25°C, and 37°C) affected bacterial physiological functions. Proteomic and metabolomic analyses were conducted on Vibrio parahaemolyticus LF1113 under different temperatures. Results and discussion A total of 2,899 proteins and 396 metabolites were identified. The differentially expressed proteins (DEPs) and differentially metabolites (DMs) were involved in Lysine degradation, metabolic pathways, ABC transporters, and microbial metabolism in diverse environments pathways. An integrated metabolomics/proteomics analysis approach was employed in this study. The analysis of both types of data information (proteins and metabolites) aids to reveal the microbial adaptive regulation in response to temperature stimuli. The study can further help clinical research of V. parahaemolyticus from the perspective of metabolomics and proteomics.

DBENet: dual-branch encoder network based on the visual state space model for semantic segmentation of remote sensing image - Hengyou Wang; Hao Liu; Lianzhi Huo; Linlin Chen; Qiang He (International Journal of Remote Sensing, 2025)

Facile One-Pot Synthesis of Folic Acid-Derived Carbon Dots for Selective “on-off-on” Fluorescence Detection of Ag+ and Glutathione with High Sensitivity - Lijuan Chen; Yuting Ding; Changchang Chen; Xiaoyan Jiang; Danni Yang; Jingwen Li; Hong Liu; Linlin Yang (Journal of Fluorescence, 2025)

Triboelectric force feedback-based fully actuated adaptive apple-picking gripper for optimized stability and non-destructive harvesting - Jingwei Sun; Linlin Sun; Guangze Zhao; Junsheng Liu; Zixu Chen; Linlong Jing; Xinpeng Cao; Hongjian Zhang; Wei Tang; Jinxing Wang (Computers and Electronics in Agriculture, 2025)

Identifying hundredfold carbon emission gaps in multiple resource recycling routes of construction waste via process and hybrid life cycle assessment - Rui Chen; Haiyuan Wu; Junjie Li; Hao Wang; Lanxin Li; Linlin Sun; Fumin Ren (Waste Management, 2025)

Recent progress in hygroscopicity improvement strategies of protein-based films for edible food packaging - Yiyi Chen; Xiangren Meng; Linlin Zhao; Pei Peng; Ying Ma; Jing Wang (Trends in Food Science & Technology, 2025)

Experimental investigation on local scour around a cubic artificial reef in bidirectional tidal currents - Linlin Wang; Mingda Yang; Muk Chen Ong; Fenfang Zhao; Yujie Cui; Yanli Tang (Ocean Engineering, 2025)

Land use carbon emission projections in shared socioeconomic and representative concentration pathways: Relationship with urbanization in Chinese megacities - Yu Yao; Linlin Lu; Zongtang Fu; Fang Chen; Ran Wang; Qingting Li (Land Use Policy, 2025)

Efficient degradation of tetracycline using boron assistant Co3O4 activated PAA: Formation of B-O-Co and accelerated electron transfer - Peng Lu; Jialin Jiang; Linlin Miao; Yun Guo; Haizhu Chen; Shuai Zhou; Jiutao An (Journal of Environmental Chemical Engineering, 2025)

Hematopoietic responses to metal-organic frameworks in adult mice following pulmonary exposure - Min Li; Linlin Yao; Yuanyuan Wang; Jie Gao; Junjie Ma; Yaquan Liu; Yun Ding; Xuehan Zheng; Liqun Chen; Runzeng Liu; Li Zeng; Guangbo Qu; et al. (Journal of Environmental Sciences, 2025)

Sources, temporal-spatial characteristics, exposure assessment and children health risk of phthalate esters (PAEs) in household dust in China from 2000 to 2023: a review and pool analysis - Wenying Zhang; Xiaotong Zhang; Xiaomin Xie; Tingting Liu; Fengjing Song; Chengyu Chen; Chao Wang; Linlin Jiang; Hang Du; Lin Fan; Xu Han; Yiming Sun; et al. (Environmental Pollution, 2025)

Predicting and quantifying damage characteristics in mechanized harvesting: A collision-based study of apples - Zixu Chen; Linlin Sun; Linlong Jing; Xinpeng Cao; Yongxian Wang; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Postharvest Biology and Technology, 2025)

Thermodynamic drivers of rice glutenin Assembly: Multiscale analysis of Hierarchical structure and intermolecular bonding - Wanshan Yang; Huining Zhang; Haoyu Li; Yuhan Jiang; Zhiqi Wang; Menglu Yang; Sitong Liu; Yinyuan He; Bing Wang; Linlin Liu; Yan Wang; Fenglian Chen; et al. (Journal of Cereal Science, 2025)

Simultaneous N-methyl pyrrolidone and total-nitrogen removals in a single aerobic process - Fei Liu; Meng Huang; Chenyu Li; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Effects of Land-Use Change on Soil Infiltrability and Preferential Flow in Typical Low Hilly Area - Linlin Chu; Rong Ma; Yue Liu; Yan Zhao; Lidong Bi; Chen Dan (Journal of Soil Science and Plant Nutrition, 2025)

Dissolved organic matter sources in urban outfall water before and during rainfall, indicated via its fluorescence fingerprinting - Haojie Yin; Tao Huang; Bo Wang; Yingying Zhang; Jiawei Hu; Linlin Zhu; Kaining Chen (Applied Geochemistry, 2025)

Smartphone-assisted portable electrochemical sensing platform for point-of-care detection of thiocyanate using a laser-induced graphene composite electrode - Xiaoming Yuan; Linlin Chen; Ruwei Liu; Shilin Li; Xiu-wen Wu; Yunhan Ling (Analytica Chimica Acta, 2025)

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Norgestrel shows androgenic properties and triggers reproductive neuroendocrine toxicity in the testes of Pacific oysters (Crassostrea gigas) - Yan Fang; Baojun Liu; Juan Wang; Haoyang Zhong; Linlin Fan; Yuchao Huang; Changkun Chen; Songtao Lu; Tao Zheng (Journal of Hazardous Materials, 2025)

Seasonal distribution patterns of P-cycling-related microbes and its association with internal phosphorus release in the eutrophic Lake Chaohu, China - Tingting Sun; Linlin Zhu; Tao Huang; Pengliang Tao; Yan Bao; Bo Wang; Qingye Sun; Kaining Chen (Journal of Environmental Sciences, 2025)

Effect of cyanobacterial bloom proliferation on antibiotic resistance genes in the sediments of a eutrophic lake - Bo Wang; Tao Huang; Linlin Zhu; Jiawei Hu; Shaodong Ma; Qingye Sun; Kaining Chen (Environmental Research, 2025)

Ecological niche imprints the structure and network of microbial communities in Lonicera japonica Thunb - Zhaoyu Zhang; Yingda Dong; Xiao Chen; Guozhuang Zhang; Conglian Liang; Yuxin Zhou; Ziying Huang; Liping Shi; Shilin Chen; Linlin Dong; Guangfei Wei (Plant and Soil, 2025)

SIMPLE: A One-Pot RPA-Cas12b Method for Single Nucleotide Variations Identification with an Expanded Scope and Clinical Applications - Kaiming Guo; Yongkang Lai; Yiru Han; Linlin Bai; Ting Wang; Shengzhou Wang; Ziqin Zhang; Dianwei Liu; Yanju Chen; Jiulong Zhao; Yanan Pang; Feng Qian; et al. (Phenomics, 2025)

From value recognition to effective implementation: the main problems and strengthening paths of law enforcement to combat IUU fishing - Linlin Chen; Yuejun He (Frontiers in Marine Science, 2025)
As a cornerstone institutional arrangement for marine fishery resource conservation, the legal efficacy of IUU fishing prohibitions is fundamentally contingent upon the standardized enforcement capacities of fishery law enforcement personnel. This study investigates the institutional disjuncture between statutory prohibitions against illegal fishing and their practical implementation. Empirical evidence derived from 526 structured questionnaires and 195(37.1% of the 526) in-depth interviews with enforcement officers across four coastal provinces(Nearly 30% of coastal provinces in China)reveals structural contradictions within the current enforcement framework: On the one hand, cognitive dissonance regarding the ecological value of fishing bans among certain officers has precipitated deficient value internalization. On the other, skepticism about the legitimacy of legal norms has engendered multiple enforcement anomalies—including but not limited to selective enforcement, passive evidence collection, sentencing disparity, and administrative-criminal procedure linkage barriers. These institutional implementation defects substantially constrain marine ecological governance efficacy. To address this institutional predicament, a systematic governance framework is proposed: Value dimension : Establish sustainable value-shaping mechanisms through capacity-building programs to foster long-term ecological consciousness; Regulatory dimension : Develop precision-engineered administrative-criminal linkage protocols to ensure coherent legal implementation; Operational dimension : Forge a three-dimensional governance architecture integrating administrative enforcement, criminal justice, and public interest litigation to construct a comprehensive “administrative-criminal-civil” liability regime. Through synergistic advancement in value recognition reconstruction, regulatory execution reinforcement, and innovative governance practices, this tripartite approach projects to enhance IUU fishing enforcement efficacy, thereby institutionalizing sustainable utilization of marine fishery resources.

MAV-ISR: from maritime gray zone competition to norm formation - Linlin Chen (Frontiers in Marine Science, 2025)
Maritime Autonomous Vehicles-based Intelligence, Surveillance, and Reconnaissance (MAV-ISR) possesses unique and novel characteristics that distinguish it from other marine activities, providing a stark contrast with the uncertainty of its standing in international law. This ambiguity has resulted in different theoretical interpretations and practical concerns. In the South China Sea, conflicts of interest and practical confrontation between countries within and outside the region have given rise to a competitive gray zone, threatening the stability of the area. To mitigate the potential impact of the MAV-ISR gray zone on the international order, it is necessary to subject it to multidimensional evaluation. Normalizing MAV-ISR is the most thorough method for curbing its gray zone; however, this process should not be rushed. Its advancement should be a gradual process informed by a range of established methods and programs.

Occupational exposure to amorphous silica nanoparticles alters lung function and metabolomic features - Xuemin Shi; Chen Liang; LinLin Wang; Xuefeng Bai; Ruiyang Ding; Zhiwei Sun (Toxicology Letters, 2025)

Social and ecological factors on the perception of cultural ecosystem services and disservices: Insights from Shanghai, China - Rongfei Su; Shiyu Ye; Linlin Yu; Jingbin Wu; Yan Kang; Ruishan Chen (Landscape and Urban Planning, 2025)

Synergistic effects on microstructural, rheological and functional properties of starch-enhanced processed mozzarella cheese - Linlin Tang; Jialin Liu; Ke Li; Yumeng Zhang; Shaomeng Luan; Tietao Chen; Hongjuan Li; Jinghua Yu (Food Structure, 2025)

Graphite-catalyzed carbonization of biowaste unlocks energy-dense, high-rate, and long-lifespan potassium-ion batteries - Jiale Chen; Lulu Tan; Chengye Lin; Yue Bai; Xiaogang Niu; Zhe Zhang; Nan Li; Linlin Wang; Ye Wang; Xiao Ji; Yujie Zhu (Chemical Engineering Journal, 2025)

Resin tapping in Masson pine (Pinus massoniana): Response of resin yield and its product quality to film mulching and chemical stimulation treatments - Jiaqi Liang; Xiaopeng Chen; Linlin Wang; Xiaojie Wei; Kewei Mo; Zehui Xiong; Jiezhen Liang (Biomass and Bioenergy, 2025)

Identification of autophagy-related biomarkers in prostate cancer prognosis - Yancheng Di; Linlin Zhao; Lingling Zhang; Lei Chen (Human Cell, 2025)

An automated river shoreline space type identification method using remote sensing data that considers space-channel attention multi-scale features - Shijiao Qiao; Wanlai Xue; Kun Jia; Jie Li; Mu Xia; Zhulin Chen; Haiying Jiang; Bo Yuan; Guofeng Tao; Yuran Cui; Linlin Zhao; Zihang Jiang; et al. (International Journal of Remote Sensing, 2025)

Global variations of urban form: Characterization and quantification through intelligent remote sensing image analysis - Jie Chen; Geng Sun; Yongze Song; Yinxia Cao; Cheolhee Yoo; Ya Guo; Chunhong Zhao; Linlin Lu; Qihao Weng (Sustainable Cities and Society, 2025)

Insight into peroxidase-mediated Pinus massoniana resin browning, and browning inhibition strategy - Hanxiao Liu; Xiaopeng Chen; Dandan Yu; Siheng Zhang; Jiezhen Liang; Xin Li; Xiaojie Wei; Linlin Wang (Sustainable Chemistry and Pharmacy, 2025)

Study on the characteristics of an underwater vehicle pump-jet propeller under the influence of drag-reduction air - Xuanhao Shao; Jianwei Zhang; Haopeng Cai; Penglei Chen; Heng Liu; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2025)

Explicit dynamics simulation study to determine the damage patterns of apples (Red Fuji) under impact loading - Zixu Chen; Linlin Sun; Linlong Jing; Yi Liu; Jingwei Sun; Junsheng Liu; Hongjian Zhang; Jinxing Wang (Journal of Stored Products Research, 2025)

Phospholipids and phosphoprotein-encapsulated silver nanoparticles: An eco-friendly and green antibacterial agent for killing bacteria and promoting chronic wound healing - Qian Cai; Wenting Chen; Haoying Zhang; Chuyu Tang; Songjing Zhong; Qinyu Zhao; Zhuo Wang; Chao Wu; Liugen Zheng; Yuanyuan Cheng; Linlin Li (Journal of Environmental Chemical Engineering, 2025)

Construction of Fenton-like systems based on hierarchical nanoconfinement for efficient antibiotic removal - Linlin Su; Wei Hu; Xiaolun He; Chao Chen; Min Xu; Xiaoyu Yu; Yan Liu; Gang Yang; Lulu Long (Journal of Environmental Chemical Engineering, 2025)

Recovery of high-value metals from the cathode of spent lithium-ion batteries via acid leaching: A review - Kaleab Bizuneh Gebeyehu; Linlin Chen; Linjing Fan; Yanhong Chao; Wenshuai Zhu (Journal of Environmental Chemical Engineering, 2025)

The roles of Paracoccus huijuniae for enhancing denitrification with N-methyl pyrrolidone as the electron donor - Meng Huang; Songyun Chen; Fei Liu; Haiyun Zhang; Xiaobing Gao; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (International Biodeterioration & Biodegradation, 2025)

Differences in the distribution of exogenous nucleotide intake in the colon of neonatal rats and its impact on early-life metabolism, gut, gut microbiota, and skeletal development - Zhihao Qu; LiLi Zhu; Min Guo; Kexin Shang; Peijun Tian; Linlin Wang; Gang Wang; Heng Zhang; Wei Chen (Food Bioscience, 2025)

Dual-responsive gelatin/fucoidan-based membrane with colorimetric and control-released performance for meat freshness monitoring and preservation - Linlin Li; Haoran Wang; Yimeng Zhang; Wei Ji; Minmin Chen; Baocai Xu; Hualin Wang (Food Packaging and Shelf Life, 2025)

Synergizing lattice matching and transient N–Li bonds to boost sulfur redox kinetics and regulate uniform lithium deposition in practical Li–S batteries - Yantao Wang; Huiqin Chen; Wenjuan Wu; Jinlong Li; Guangxin Zhang; Chunyan Wei; Shiyu Wang; Linlin Zhang; Yanping Zheng; Huanhuan Li (Chemical Engineering Journal, 2025)

Hydrological Connectivity Induces Changes in Macrobenthos Functional Feeding Groups in a Typical Tidal Creek System of the Yellow River Delta - Qinglu Fu; Li Chen; Debin Sun; Jiao Wang; Jing Chen; Baoquan Li; Linlin Chen (Wetlands, 2025)

Climate evolution and its driving factors in the Tethys Sea region during the Cenozoic - Jiangbo Meng; Jiagang Zhao; Linlin Chen; Paul J. Valdes; Alex Farnsworth; Svetlana Popova; Mine Sezgül Kayseri-Özer; Gaurav Srivastava; Jian Huang; Tao Su; Zhekun Zhou; Shufeng Li (Science China Earth Sciences, 2025)

The Receptor for Advanced Glycation End-products in the Mouse Anterior Cingulate Cortex is Involved in Neuron‒Astrocyte Coupling in Chronic Inflammatory Pain and Anxiety Comorbidity - Wei Jiang; Minmin Gong; Linlin Shen; Chenghui Yu; Huaizhen Ruan; Penghui Chen; Shihao Gao; Zhi Xiao (Molecular Neurobiology, 2025)

Nine-year biochar history increases topsoil nitrogen stocks and reduces the refractory organic nitrogen fractions in deep soils - Di Wang; Shuai Liu; Liwei Hao; Qi Yue; Linlin Jiang; Yu Lan; Wenfu Chen (Journal of Soils and Sediments, 2025)

Optimized Soil Nitrogen Management for Enhanced Photosynthetic Efficiency and Yield in High-Quality Japonica Rice in the Taihu Lake Region - Yunsheng Song; Yulin Xie; Minghui Dong; Fei Chen; Xiuliang Jin; Yajie Hu; Junrong Gu; Peifeng Chen; Yongliang Zhu; Linlin Shi; Yixiao Wang (International Journal of Plant Production, 2025)

Spegazzinia menglaensis, A Novel Species of Didymosphaeriaceae from Air in China - Xingwen Dai; Linlin Fang; Tong Chen; Manyao Feng; Zefen Yu (Current Microbiology, 2025)

The promotion mechanism of ammonia-based CO2 capture by hydroxyl and amine additives: A molecular dynamics and DFT study - Jiaxing Du; Wu Yang; Linlin Xu; Jiaming Chen; Zijian Song; Ben Wang; Lushi Sun (Fuel, 2025)

Dietary emulsifier Polysorbate 80-induced lipotoxicity promotes intestinal senescence - Linlin He; Lan Zhang; Fanyi Meng; Jingge Wei; Fei Chen; Siqi Qin; Ge Jin; Hailong Cao (Food Research International, 2025)

The influence of different drying methods on the molecular structure and digestive resistance of type 3 resistant starch (RS3) - Qing Su; Linlin Sun; Lirong Chen; Xingya Wang; Kaichang Liu; Kuijie Gong (Food Chemistry, 2025)

Low-molecular-weight carrageenan prepared by photocatalysis-freeze-thaw circle and its in vivo distribution after oral administration - Chen Song; Zhejin Chen; Linlin Wang; Nan Wang; Jie Tian; Chunqing Ai; Shuang Song (Food Hydrocolloids, 2025)

Spatiotemporal variations of dissolved nitrous oxide concentrations in small water bodies in a typical urban landscape in eastern China - Xuebing Chen; Yuye Shen; Yihong Liu; Fangfang Zhang; Linlin Tian; Jing Wang; Yanjiang Cai; Yan Li; Scott X. Chang (Environmental Pollution, 2025)

Size-dependent internalization of gold nanoparticles in individual Tetrahymena thermophila characterized by single-cell mass cytometry - Junjie Ma; Yaquan Liu; Liu Zhang; Linlin Yao; Yun Ding; Hua Qin; Ziniu Wang; Xuehan Zheng; Xinyue Yang; Haijiang Tian; Li Zeng; Liqun Chen; et al. (Environmental Pollution, 2025)

Computational fluid dynamics and machine learning assisted Al-LDH adsorbent reactor design for lithium recovery from salt lakes - Jiangtao Yu; Minmeng Tang; Peng Cui; Jianquan Deng; Haiying Mi; Li Zhang; Linlin Chen; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2025)

The role of immunoglobins in atherosclerosis development; friends or foe? - Linlin Zhang; Peize Li; Yuhui Li; Wantong Qu; Yanyu Shi; Tianyang Zhang; Ying Chen (Molecular and Cellular Biochemistry, 2025)

Transcranial Magnetic Stimulation Alleviates Spatial Learning and Memory Impairment by Inhibiting the Expression of SARM1 in Rats with Cerebral Ischemia–Reperfusion Injury - Linlin Jiang; Yule Wang; Yingxi He; Ying Wang; Hao Liu; Yu Chen; Jingxi Ma; Ying Yin; Lingchuan Niu (NeuroMolecular Medicine, 2025)

Development and validation of a prediction model for the depressive symptom risk in commercial airline pilots - Jie Zhang; Xuhua Chen; Lin Zhang; Haodong Qi; Erliang Zhang; Minzhi Chen; Yiran Wang; Yunfei Li; Yan Chen; Qingqing Duan; Feng Shi; Linlin Wang; et al. (EPMA Journal, 2025)

Functionality-dependent removal efficiency and mechanisms of polystyrene microplastics by a robust magnetic biochar - Xiaotong Duan; Xian Chen; Linlin Shi; Yiran Cao; Yuechang Liang; Tianyu wang; Chen Huang; Yuxin Cao (Journal of Environmental Chemical Engineering, 2025)

Utilizing zeolitic imidazolate framework-8 for enhanced carbon dioxide/methane separation and improved carbon dioxide methanation performance - Weiqi Zhang; Xin Kong; Linlin Bo; Delin Yin; Zhichun Zhang; Xiaojun Fan; Hongping Chen; Jin Yuan (Bioresource Technology, 2025)

Cation Channel TMEM63A Autonomously Facilitates Oligodendrocyte Differentiation at an Early Stage - Yue-Ying Wang; Dan Wu; Yongkun Zhan; Fei Li; Yan-Yu Zang; Xiao-Yu Teng; Linlin Zhang; Gui-Fang Duan; He Wang; Rong Xu; Guiquan Chen; Yun Xu; et al. (Neuroscience Bulletin, 2025)
Accurate timing of myelination is crucial for the proper functioning of the central nervous system. Here, we identified a de novo heterozygous mutation in TMEM63A (c.1894G>A; p. Ala632Thr) in a 7-year-old boy exhibiting hypomyelination. A Ca 2+ influx assay suggested that this is a loss-of-function mutation. To explore how TMEM63A deficiency causes hypomyelination, we generated Tmem63a knockout mice. Genetic deletion of TMEM63A resulted in hypomyelination at postnatal day 14 (P14) arising from impaired differentiation of oligodendrocyte precursor cells (OPCs). Notably, the myelin dysplasia was transient, returning to normal levels by P28. Primary cultures of Tmem63a −/− OPCs presented delayed differentiation. Lentivirus-based expression of TMEM63A but not TMEM63A_A632T rescued the differentiation of Tmem63a −/− OPCs in vitro and myelination in Tmem63a −/− mice. These data thus support the conclusion that the mutation in TMEM63A is the pathogenesis of the hypomyelination in the patient. Our study further demonstrated that TMEM63A-mediated Ca 2+ influx plays critical roles in the early development of myelin and oligodendrocyte differentiation.

Influence of ocean-atmosphere interactions on typhoon track and intensity: a case study for typhoon “Hato” (1713) - Yonghang Chen; Yu Wei; Yunxia Zheng; Xianwen Wu; Qiong Liu; Ruixue Li; Linlin Sun; Bingke Zhao; Sijie Yin; Haicheng Liu; Xiaoyu Li (Natural Hazards, 2025)

Environmental heterogeneity drives the spatial distribution of macrobenthos in the Yellow River Delta wetland - Qinglu Fu; Jiao Wang; Debin Sun; Jianyu Chi; Wenzheng Fan; Yu Li; Yilin Wang; Baoquan Li; Linlin Chen (Aquatic Sciences, 2025)

Current and future thermal effects and spatial optimization modelling of urban greenspace in megacity - Rundong Feng; Shenghe Liu; Fuyuan Wang; Bin Chen; Kaiyong Wang; Linlin Xu (Sustainable Cities and Society, 2025)

Host selection shapes structure and network of microbial community of Epimedium plants along the soil–rhizosphere–plant continuum - Zhaoyu Zhang; Ziying Huang; Xiao Chen; Guozhuang Zhang; Mengzhi Li; Anning Li; Xiaolin Lin; Yuxin Zhou; Yu Zhang; Shilin Chen; Linlin Dong; Guangfei Wei (Rhizosphere, 2025)

GLOSTFM: A global spatiotemporal fusion model integrating multi-source satellite observations to enhance land surface temperature resolution - Qingyan Meng; Shize Chen; Linlin Zhang; Xiaolin Zhu; Yeping Zhang; Peter M. Atkinson (Remote Sensing of Environment, 2025)

Cyclic plasticity of hardened oil well cement paste: A nonlinear kinematic hardening perspective - Linlin Wang; Shuo Chen; Shuitao Zhang; Jiyun Shen; Rongwei Yang (Geomechanics for Energy and the Environment, 2025)

Physicochemical properties and structure of rice dough and protein based on TGase combined with sodium metabisulfite modification - Xuyang Ren; Wanshan Yang; Huining Zhang; Yang Yu; Xiaofeng Hu; Hongchen Fan; Linlin Liu; Mingshou Lv; Ying Sun; Yanguo Shi; Yanling Hao; Fenglian Chen (Food Chemistry, 2025)

Enhancement of farinographic characteristics of rice dough and rice bread quality with combined chemical and enzymatic approaches - Huining Zhang; Wanshan Yang; Yuhan Jiang; Haoyu Li; Menglu Yang; Zhiqi Wang; Bing Wang; Linlin Liu; Hongchen Fan; Fenglian Chen; Ying Liu (Food Bioscience, 2025)

Novel NIR-Ⅱ-Activated titanate-supported iridium nanoplatform delivers multimodal antitumor therapy synergistic with PD-1 inhibition in TNBC - Peixin Du; Xian Jiang; Zihan Xu; Linlin Song; Meixu Chen; Yujie Zhao; Jing Yu; Tianyue Xu; Ting Sun; Huang Zhu; Hubing Shi; Jing Jing (Chemical Engineering Journal, 2025)

Butyrylated modification of corn starch alleviates autism-like behaviors by modulating 5-hydroxytryptamine metabolism and gut-brain neural activity - Wentian Li; Qingmin Kong; Min Guo; Linlin Wang; Peijun Tian; Jingyu Lu; Jianxin Zhao; Wei Chen; Gang Wang (Carbohydrate Polymers, 2025)

TRIM21 Promotes Endothelial Cell Activation via Accelerating SOCS3 Ubiquitination Degradation in Atherosclerosis - Zhenxuan Hao; Yihuan Wang; Linlin Chen; Yanjun Zhou; Dezhou Fang; Wenxiang Yao; Lili Xiao; Yanzhou Zhang (Cardiovascular Toxicology, 2025)

A real-time vision guidance method for autonomous longan picking by the UAV - Hengxu Chen; Kaixuan Wu; Hengyi Lin; Haobo Zhou; Zhengqi Zhou; Yuju Mai; Linlin Shi; Meiqi Zhang; Zhe Ma; Peihan Lin; Jun Li (Computers and Electronics in Agriculture, 2025)

The impact of energy metabolic pattern on household carbon emissions: A spatio-temporal perspective in Guangdong-Hong Kong-Macao Greater Bay Area - Lei Chen; Jiahan Luo; Guotian Cai; Linlin Xia; Yongyang Wang; Linyu Xu (Sustainable Cities and Society, 2025)

Rapid, green and semi-automated PT-μSPE for antidepressants analysis in urine and plasma using melt-blown polypropylene from disposable face masks as sorbent - Qianwei Li; Bowen Deng; Ru Feng; Di Chen; Linlin Hua (Sustainable Chemistry and Pharmacy, 2025)

Influence of atomic coordination on the activity of lattice oxygen and catalytic oxidation of toluene over regular Cu2O crystalline - Linlin Deng; Mingtai Li; Xin Gao; Xiaokun Yi; Yang Zhao; Yulong Yang; Zitong Zhao; Jiarui Chen; Baojuan Dou; Feng Bin (Journal of Hazardous Materials, 2025)

The role of telomere shortening in ambient ozone exposure-related insulin resistance - Ruiying Li; Gongbo Chen; Wei Liao; Yinghao Yuchi; Xiaohuan Yang; Ziyuan Zhang; Xiaotian Liu; Zhenxing Mao; Linlin Li; Jiahui Zhao; Huijun Li; Wenqian Huo; et al. (Journal of Hazardous Materials, 2025)

Improvement of 3D printing and subsequent microwave freeze-drying solidification accuracy of pineapple gel-based inks: Infill percentage control and internal models design - Yunfei Bao; Wenchao Liu; Linlin Li; Guangyue Ren; Chung Lim Law; Weiwei Cao; Jiayao Wang; Zhenjiang Luo; Junliang Chen; Xu Duan (Journal of Food Engineering, 2025)

Using the Forel-Ule index (FUI) to track the water quality of subsidence water bodies across the life cycle of coal mining in eastern China - Wenqi Chen; Lijuan Chen; Yongping Wei; Linlin Ruan; Yanhua Fu; Wei Li; Tingting He; Wu Xiao (Journal of Environmental Management, 2025)

About 868 cal. yr BP tsunami event at the northern South China Sea revealed from offshore sediments - Yuming Wang; Xiaohong Chen; Adam D. Switzer; Linlin Li; Yang Xu; Yukun Wang; Elaine Tan; Peizhen Zhang (Global and Planetary Change, 2025)

Earthquake-induced Submarine Landslides (EQISLs) and a comparison with their Terrestrial Counterparts: Insights from a New Database - Peng Du; Linlin Li; Achim Kopf; Dawei Wang; Kejie Chen; Huabin Shi; Weitao Wang; Xiaoyi Pan; Gui Hu; Peizhen Zhang (Earth-Science Reviews, 2025)

In2O3 modification mitigates Jahn-Teller effect in LiMn2O4 enhancing lithium extraction efficiency and stability - Linlin Chen; Linjing Fan; Delin Lan; Jun Gu; Chen Xiaojun; Haiyan Ji; Yanhong Chao; Peiwen Wu; Wenshuai Zhu (Chemical Engineering Journal, 2025)

Spatiotemporal evolution of wildfire activity during the Paleocene-Eocene Thermal Maximum in China - Xue-Ting Wang; Zuoling Chen; Linlin Cui; Xu Wang (Science China Earth Sciences, 2025)

Lactic acid bacteria in relieving constipation: mechanism, clinical application, challenge, and opportunity - Tong Zhang; Wenxu Liu; Huimin Lu; Ting Cheng; Linlin Wang; Gang Wang; Hao Zhang; Wei Chen (Critical Reviews in Food Science and Nutrition, 2025)

Contribution of mitochondria to postmortem muscle tenderization: a review - Feng Huang; Zhenjiang Ding; Jinsong Chen; Bing Guo; Linlin Wang; Chunmei Liu; Chunhui Zhang (Critical Reviews in Food Science and Nutrition, 2025)

Salmonella enterica serovar typhimurium effectors spiA and spiC promote replication by modulating iron metabolism and oxidative stress - Keyuan Chen; Jing Wang; Ting Hu; Yiqing Zhao; Yi Wu; Xue Wang; Wei Li; Guiyan Yang; Linlin Zhang; Jiufeng Wang; Yaohong Zhu (Veterinary Microbiology, 2025)

Metagenomics and metaproteomics reveal the effects of sludge types and inoculation modes on N,N-dimethylformamide degradation pathways and the microbial community involved - Yunchuan Xian; Linlin Cao; Yuxiang Lu; Qiuhong Li; Chengyuan Su; Yuan He; Guangrong Zhou; Shenglong Chen; Shu Gao (Journal of Hazardous Materials, 2025)

Optimization model for co-pyrolytic synergy: A case study in starch sludge with chicken manure and comprehensive investigation combining kinetics, bio-products characterization, and DFT-based decomposition pathways - Hairong Mo; Xiaopeng Chen; Tongxi Mo; Chenghong Wu; Wanbin Wei; Yuanjie Wu; Qinxin Li; Jiezhen Liang; Linlin Wang (Fuel, 2025)

Dietary nucleotides drive changes in infant fecal microbiota in vitro and gut microbiota-gut-brain development in neonatal rats: A potential “nitrogen source” for early microbiota growth - Zhihao Qu; Bo Zhang; Guopeng Lin; Min Guo; Peijun Tian; Linlin Wang; Wei Chen; Heng Zhang; Gang Wang (Food Chemistry, 2025)

Plant extracellular vesicles contribute to the amplification of immune signals during systemic acquired resistance - Wenjing Wang; Junsong Zhang; Liying Pan; Zijia Liu; Weiwei Yi; Xiaolong Xing; Linlin Bai; Qiao Liu; Qingbin Chen; Lingyu Mi; Qingfeng Zhou; Dongli Pei; et al. (Plant Cell Reports, 2025)

BDNF-VGF Pathway Aggravates Incision Induced Acute Postoperative Pain via Upregulating the Neuroinflammation in Dorsal Root Ganglia - Wenjing Zhao; Lulin Ma; Daling Deng; Linlin Han; Feng Xu; Tianhao Zhang; Yafeng Wang; Shiqian Huang; Yuanyuan Ding; Shaofang Shu; Xiangdong Chen (Molecular Neurobiology, 2025)

Pharmacokinetics of seven major components in Aβ1-42-treated rats after oral administration of an aqueous extract of Curculiginis Rhizoma and Epimedii Folium - Junzuo Zheng; Jun Wang; Linlin Chen; Xuelian Jiang; Xuesong Zhang; Wenqi Ai; Yuman Xie; Ping Wang; Zhou Lan; Xiaoping Ding (Journal of Natural Medicines, 2025)

Towards a dialectical understanding of rural resilience and rural sustainability: bibliometric analysis and evidence from existing literature and China - Huan Li; Tao Xu; Chen Yang; Yang Fu; Changyan Wu; Linlin Zhang; Guoliang Xu; Wei Wang (Environment, Development and Sustainability, 2024)

Distribution, transport and ecological risk prediction of organophosphate esters in China seas based on machine learning - Rui Chen; Wenyang Huang; Linlin Sun; Jingyan Yang; Tiantian Ma; Rongguang Shi (Science of The Total Environment, 2024)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

Organotin exposure and DNA methylation in non-syndromic cleft lip and palate: Integrating findings from case-control studies and animal experiments - Yongyan Chen; Qianhui Cheng; Sainan Li; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Science of The Total Environment, 2024)

The mediating role of abnormal ZEB1 methylation in the association between nickel exposure and non-syndromic orofacial cleft - Yongyan Chen; Yaquan Pan; Lijun Liu; Yingnan Guo; Lei Jin; Aiguo Ren; Linlin Wang (Reproductive Toxicology, 2024)

The complete genome sequence of Streptomyces sp. FIM 95-F1, a marine actinomycete that produces the antifungal antibiotic scopafungin - Peng Fei; Lin Yangjun; Zhuang Yuee; Lin Ping; Liu Chengzhi; Chen Linlin; Jiang Hong; Lian Yunyang; Zhang Wenzhou; Huang Youxia (Marine Genomics, 2024)

Roles of mTOR-p70S6K signaling pathway and HO-1 in ethylbenzene-induced hepatoxic effects in L02 cells - Siyu Liu; Linlin Chen; Hui Peng; Qiang Zhang; Qiang Zeng; Bo Cui; Ming Zhang (Food and Chemical Toxicology, 2024)

Low level exposure to BDE-47 facilitates the development of prostate cancer through TOP2A/LDHA/lactylation positive feedback circuit - Linlin Tian; Nan Zhou; Ning Zhao; Mengkai Qiao; Min He; Ziqing Mao; Wenjiong Xu; Dandan Xu; Yan Wang; Yan Xu; Tong Chen (Environmental Research, 2024)

Prenatal co-exposure to phthalate metabolites and bisphenols among non-syndromic cleft lip and/or palate in offspring - Sainan Li; Haiyan Zhu; Chen Yang; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Precise fabrication and superior combustion properties of n-B pomegranate microspheres based on a new dissolution-dispersion-coating method - Yushu Xiong; Baoxuan Li; Yinghong Wang; Linlin Liu; Jie Huang; Suhang Chen; Fengqi Zhao; Kangzhen Xu (Chemical Engineering Journal, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Effects of nitrogen fertilization on nitrogen metabolism and grain protein in premium-tasty japonica rice - Yunsheng Song; Minghui Dong; Yajie Hu; Linlin Shi; Junrong Gu; Yuxuan Wang; Shikun Wang; Penghui Cao; Yajie Yu; Yongliang Zhu; Yulin Xie; Zhongying Qiao; et al. (Cereal Research Communications, 2024)

Evaluating the phase evolution of CMIP GCMs for agricultural climate-change impact assessments in China - Linlin Yao; Qian Tan; Guanhui Cheng; Shuping Wang; Bingming Chen (Agricultural and Forest Meteorology, 2024)

Genes and Pathways Underpinning Klinefelter Syndrome at Bulk and Single-Cell Levels - Linlin Tian; Yan Yu; Ziqing Mao; Dandan Xu; Hongbo Zhang; Mengkai Qiao; Tong Chen; Wen Liu (Biochemical Genetics, 2024)

Biocontrol potential of plant growth-promoting rhizobacteria against plant disease and insect pest - Qinhao Jian; Tongrui Zhang; Yingying Wang; Li Guan; Linlin Li; Longna Wu; Shiyan Chen; Yumei He; Hong Huang; Shugang Tian; Hu Tang; Litang Lu (Antonie van Leeuwenhoek, 2024)

Prospective study on the joint effect of persistent organic pollutants and glucose metabolism on chronic kidney disease: Modifying effects of lifestyle interventions - Dandan Wei; Jiayu Shi; Haoran Xu; Yao Guo; Xueyan Wu; Zhiwei Chen; Taimeng Chen; Huilin Lou; Erbao Han; Guozhen Han; Yumeng Yan; Xiaotian Liu; et al. (Science of The Total Environment, 2024)

Estimating global 0.1° scale gridded anthropogenic CO2 emissions using TROPOMI NO2 and a data-driven method - Yucong Zhang; Shanshan Du; Linlin Guan; Xiaoyu Chen; Liping Lei; Liangyun Liu (Science of The Total Environment, 2024)

Artificial river flow regulation triggered spatio-temporal changes in marine macrobenthos of the Yellow River Estuary - Debin Sun; Jiao Wang; Qinglu Fu; Linlin Chen; Jing Chen; Teng Sun; Baoquan Li (Marine Environmental Research, 2024)

Migration of depleted uranium from a corroded penetrator in soil vadose zone in Bosnia and Herzegovina - Cui Li; Yanru Liang; Yin Ye; Fan Chen; Markus Astner; David J. Paterson; Yanlong Chen; Linlin Wang; Paul Guagliardo; Matvei Aleshin; Mario Burger; Peter M. Kopittke; et al. (Journal of Hazardous Materials, 2024)

Characteristics of iron-sulfur metabolism and acid-producing microorganisms in groundwater contaminated by acid mine drainage in closed coal mines - Yanchang Huang; Ping Lu; Feng Zhang; Hao Chen; Wenliang Zhang; Linlin Lin; Hepeng Xu; Haoran Ding; Tianhang Cheng (Groundwater for Sustainable Development, 2024)

Fabrication, characterization, and antibacterial properties of sodium alginate/chito-oligosaccharide gel beads - Nan Wang; Jie Tian; Linlin Wang; Chen Song; Chengrong Wen; Yinghuan Fu; Shuang Song (Food Hydrocolloids, 2024)

Changes in salinity and vegetation growth under different land use types during the reclamation in coastal saline soil - Linlin Chu; Si Yuan; Dan Chen; Yaohu Kang; Hiba Shaghaleh; Mohammad K. Okla; Hamada AbdElgawad; Yousef Alhaj Hamoud (Chemosphere, 2024)

Decadal variation and temporal stability of the macrobenthic community in the Bohai Sea, China - Shaoyu Jiang; Jiao Wang; Wenzheng Fan; Linlin Chen; Jing Chen; Baoquan Li (Marine Pollution Bulletin, 2024)

Exploring the paradox of densification and greening in China’ s old cities - Wenqi Chen; Yuxuan Qiu; Linlin Ruan; Chun Ren; Chunfeng Zhou; Sucheng Xu; Kechao Wang; Tingting He; Wu Xiao (Urban Forestry & Urban Greening, 2024)

Transcriptomic analysis uncovers a biphasic response to precocious Eimeria acervulina infection in chicken duodenal tissue - Ning Zhang; Jie Liu; Yuanyuan Zhang; Linlin Chen; Sixin Zhang; Xianyong Liu; Xinming Tang; Xiaolong Gu; Shiyi Chen; Xun Suo (Veterinary Parasitology, 2024)

Effect of silicon on the distribution and speciation of uranium in sunflower (Helianthus annuus) - Linlin Wang; Yanru Liang; Song Liu; Fan Chen; Yin Ye; Yanlong Chen; Jingjing Wang; David J. Paterson; Peter M. Kopittke; Yuheng Wang; Cui Li (Journal of Hazardous Materials, 2024)

Characterization of low-molecular-weight fucoidan prepared by photocatalysis degradation and its regulation effect on metabolomics of LPS-stimulated macrophages - Lilong Wang; Linlin Wang; Jinhe Tian; Chunhong Yan; Chen Song; Shuangcai Xiao; Shuang Song (Food Bioscience, 2024)

Multistage regulation of LiMn2O4 electrode for electrochemical lithium extraction from salt-lake - Jun Gu; Linlin Chen; Linjing Fan; Guiling Luo; Xiaowei Li; Xiaojun Chen; Haiyan Ji; Yanhong Chao; Wenshuai Zhu (Desalination, 2024)

3D-printed devices for continuous-flow lithium recovery of brines - Jiangtao Yu; Jie Zhu; Zhuo Han; Peng Cui; Haiying Mi; Anan Zhang; Linlin Chen; Xiaowei Li; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2024)

Functional molecules surface segregation engineering in electrospinning: Design, regulation, and applications - Linlin Cao; Chen Qu; Jingchong Liu; Wenhui Li; Lihua Jiang; Boyu Jing; Chuandong Wu; Jiemin Liu (Chemical Engineering Journal, 2024)

Turnover structures in macrobenthic communities rather than nestedness in the Yellow River Delta wetland, China - Jiao Wang; Shaoyu Jiang; Debin Sun; Jing Chen; Baoquan Li; Linlin Chen (Aquatic Sciences, 2024)

Daily trunk radial growth patterns in relation to precipitation in orange trees in the dry-hot valley region of Southwest China - Xuehui Wei; Dianyu Chen; Panpan Hou; Xiaotao Hu; Lucheng Qiu; Jingying Zhang; Xingwu Duan; Linlin Zhang; Jing Guo (Journal of Hydrology, 2024)

Association between spectrum of mycotoxins and semen quality: A cross-sectional study in Beijing, China - Chen Yang; Xiao Ning; Baojun Wang; Tian Tian; Yongyan Chen; Le Ma; Linlin Wang (Journal of Hazardous Materials, 2024)

Quantify the extensive crop damage and grain losses caused by underground coal mining subsidence in eastern China - Wenqi Chen; Wu Xiao; Tingting He; Linlin Ruan; Yanling Zhao; Zhenqi Hu (Journal of Cleaner Production, 2024)

Transformation and environmental risk of 90Sr and 137Cs under extreme rainstorm at a proposed nuclear facility site in China - Jun Zhu; Ying Hao; Chao Chen; Ting Wang; Ke Chen; Linlin Zhang; Aiming Zhang; Tian Xie; Qiulan Zhang (Journal of Environmental Radioactivity, 2024)

A multi-omics-based investigation into the regulation of phenolics in fresh maize kernels at different developmental stages - Xiaomin Tian; Di Han; Linlin Sun; Yuqiu Guo; Kaichang Liu; Lirong Chen; Kuijie Gong (Journal of Cereal Science, 2024)

Influence of mountain orientation on precipitation isotopes in the westerly belt of Eurasia - Longhu Chen; Guofeng Zhu; Qin Qin Wang; Linlin Ye; Xinrui Lin; Siyu Lu; Yinying Jiao; Rui Li; Gaojia Meng; Yuhao Wang; Jiangwei Yang; Chen Jia (Global and Planetary Change, 2024)

Elemental mercury removal by copper-containing brominated pyrolytic chars derived from waste printed circuit boards - Gan Wan; Tao Chen; Linlin Xu; Lushi Sun (Fuel, 2024)

Intelligent multi-colorimetric cellulose acetate/cobalt-based metal-organic framework antibacterial film and its application to pork preservation - Qianlan Tao; Yewen Xiao; Xuan Hu; Huaiting Pang; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Food Packaging and Shelf Life, 2024)

Thermal interface materials with low modulus and high thermal conductivity by manipulating multi-branched PDMS network: The disentanglement and entanglement effect of dangling chain - Zhian Zhang; Zhibin Wen; Jiashuo Sheng; Chen Zeng; Jianfeng Fan; Linlin Ren; Xiaoliang Zeng; Rong Sun; Peng Chen (Chemical Engineering Journal, 2024)

Boosting TNBC immune checkpoint blockade with an imaging-therapy coupled ozone delivery nano system - Linlin Song; Zhihui Liu; Xiujing He; Tianyue Xu; Meixu Chen; Zihan Xu; Haina Zhao; Jiaojiao Suo; Hong Wang; Zhankun Yang; Shenglan You; Xiaoting Chen; et al. (Chemical Engineering Journal, 2024)

High-amylose starch-based gel as green adhesive for plywood: Adhesive property, water-resistance, and flame-retardancy - Yaoxing Chen; Yongjing Rao; Peng Liu; Linlin Wu; Guojie Zhang; Jianguo Zhang; Fengwei Xie (Carbohydrate Polymers, 2024)

Elevated lead mobility in sediments of a eutrophic drinking water reservoir during spring and summer seasons: Insights from isotopic signatures - Zhenghua Tao; Guogan Peng; Fengyuan Chen; Qingjun Guo; Rongfei Wei; Ke Pan; Yinan Deng; Linlin Jiao; Zhen Zhang; Shanshan Chen; Tianxiang Xia (Journal of Hazardous Materials, 2024)

An integrated investigation combining network pharmacology and computer simulation dissects the potential mechanism of anti-obesity of Monascus pigments (MPs) - Jiaxing Li; Huijing Zhang; Linlin Xu; Huiqian Liu; Chenchen Qi; Chengtao Wang; Wei Chen (Food Bioscience, 2024)

A novel multifunctional photocatalytic membrane based on ternary heterojunction TiO2@PDA@BiOBr for biochemical oily wastewater purification - Wei Ji; Yewen Xiao; Feng Xiao; Linlin Li; Minmin Chen; Hualin Wang (Chemical Engineering Journal, 2024)

Myosin Va-dependent Transport of NMDA Receptors in Hippocampal Neurons - Ru Gong; Linwei Qin; Linlin Chen; Ning Wang; Yifei Bao; Wei Lu (Neuroscience Bulletin, 2024)
N-methyl-D-aspartate receptor (NMDAR) trafficking is a key process in the regulation of synaptic efficacy and brain function. However, the molecular mechanism underlying the surface transport of NMDARs is largely unknown. Here we identified myosin Va (MyoVa) as the specific motor protein that traffics NMDARs in hippocampal neurons. We found that MyoVa associates with NMDARs through its cargo binding domain. This association was increased during NMDAR surface transport. Knockdown of MyoVa suppressed NMDAR transport. We further demonstrated that Ca 2+ /calmodulin-dependent protein kinase II (CaMKII) regulates NMDAR transport through its direct interaction with MyoVa. Furthermore, MyoVa employed Rab11 family-interacting protein 3 (Rab11/FIP3) as the adaptor proteins to couple themselves with NMDARs during their transport. Accordingly, the knockdown of FIP3 impairs hippocampal memory. Together, we conclude that in hippocampal neurons, MyoVa conducts active transport of NMDARs in a CaMKII-dependent manner.

Extraction of organic solvents and preferential recovery of lithium from spent lithium-ion batteries by in-situ carbothermal reduction - Jian Zou; Ruihan Zhang; Yali Zhang; Linlin Chen; Yaoguo Huang; Xianfu Sun (Process Safety and Environmental Protection, 2024)

Provenance signature and tectono–sedimentary setting of the Permian Shihezi formation (Ordos basin, China): Insights from geochemistry and detrital zircon U–Pb dating - Shuyue Zhu; Lei Liu; Linlin Wang; Zhiwei Wang; Jianling Hu; Jingqi Zhang; Chenggong Zhang; Junxing Zhao; Hongde Chen (Marine and Petroleum Geology, 2024)

Volcanic lithofacies control the space in unconventional, rhyolitic hydrocarbon reservoirs: The Hailar Basin, NE China - Yuting Chen; Han Zheng; Guido Ventura; Linlin Zeng; Wei Pi; Yu Wei (Marine and Petroleum Geology, 2024)

An evaluation on the shrinkage deformation characteristics of Chinese yam during multiphase microwave drying based on digital image processing - Mengmeng Yang; Linlin Li; Wenchao Liu; Weiwei Cao; Junliang Chen; Guangyue Ren; Ke Gao; Chung Lim Law; Xu Duan (Innovative Food Science & Emerging Technologies, 2024)

Chromium levels in placental tissue and neural tube defects: Association and mechanistic study - Yongyan Chen; Yingnan Guo; Chengrong Wang; Jufen Liu; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Environmental Pollution, 2024)

Integrated assessment of trace elements in a marine ranching area based on multi-species and multi-level biomarkers: a case study in China’s national-level marine ranching demonstration area - Mingzhu Li; Zhixu Chen; Ming Li; Jiugang Zhang; Bingqing Xu; Yanyan Yang; Xiangfei Li; Linlin Fan; Baojun Liu; Tao Zheng; Yan Fang; Fan Li (Frontiers in Marine Science, 2024)
The goal of this study was to evaluate the trace element pollution in a marine ranching area in China based on molecular responses (expression of metallothionein and antioxidant enzyme genes), and biochemical biomarkers (metallothionein content, antioxidant enzyme activities, and malonaldehyde level) in four indicator species. We collected samples of two fish ( Lateolabrax maculatus and Sebastes schlegelii ), one crustacean ( Charybdis japonica ), and one gastropod ( Rapana venosa ) from the western Furong Island marine ranching area and from an adjacent area in March 2022 and measured the trace element content in these indicator species as well as in the seawater and sediment. We found that the bioaccumulation characteristics of trace elements and the response patterns of biomarkers were species specific. Moreover, not every biomarker was significantly correlated with environmental trace element content. We then established two biomarker combinations indicative of trace element pollution in seawater and sediment, respectively, based on the correlation between biomarkers and trace element contents. The selected biomarkers were integrated using integrated biomarker response version 2 (IBRv2). IBRv2 values in the studied marine ranching area were lower than those in the adjacent area. Additionally, these values were consistent with the bioaccumulation of trace elements in the indicator species, the integrated trace element pollution index for seawater, and the potential risk index for sediment. These results show that this multi-biomarker and multi-species IBRv2 approach provided a comprehensive diagnosis of trace element pollution in the marine ranching area. Therefore, its application may be beneficial for marine environmental monitoring and management in view of the ecotoxicological impact of pollutants on organisms.

A robust transformer-based pipeline of 3D cell alignment, denoise and instance segmentation on electron microscopy sequence images - Jiazheng Liu; Yafeng Zheng; Limei Lin; Jingyue Guo; Yanan Lv; Jingbin Yuan; Hao Zhai; Xi Chen; Lijun Shen; LinLin Li; Shunong Bai; Hua Han (Journal of Plant Physiology, 2024)

Recent progress in the antidegradation strategies of two-dimensional transition metal carbides (MXenes) - Ying Li; Yudi Li; Linlin Zhao; Siyu Chen; Siren Guo; Xulin Yang; Pan Wang; Kui Li; Fan Lei; Wei Feng; Zihao Mou; Hanjun Wei (Journal of Environmental Chemical Engineering, 2024)

A novel metal–organic framework based electrochemical immunosensor for the rapid detection of Salmonella typhimurium detection in milk - Ke Zhan; Linlin Chen; Shanshan Li; Qiuying Yu; Zheng Zhao; Junwei Li; Yunrui Xing; Hongtao Ren; Na Wang; Gaiping Zhang (Food Chemistry, 2024)

Determination of chloropropanol esters and glycidyl esters in instant noodles based on solid-phase microextraction with chitosan-β-cyclodextrin coated fiber - Linlin Bian; Xue Ge; Senwei Feng; Guangxuan Chen; Kefeng Li; Xu Wang (Food Chemistry, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

Imbalances in the gut microbiota and metabolome are associated with functional constipation in pregnancy - Ruili Pan; Ying Chen; Guopeng Lin; Haojue Wang; Xiaopeng Xu; Linlin Wang; Peijun Tian; Jianxin Zhao; Wei Chen; Gang Wang (Food Bioscience, 2024)

Response of photosynthetic characteristics and antioxidant system in the leaves of safflower to NaCl and NaHCO3 - Linlin Song; Yongliang Yu; Hongzhi Chen; Yuwei Feng; Shuo Chen; Huihui Zhang; Haijia Zhou; Li Meng; Yue Wang (Plant Cell Reports, 2024)

Effects of Nitrogen Fertilizer Reduction Combined with Foliar Fertilizer Application on the Physiological Characteristics and Yield of High-Quality Japonica Rice - Yunsheng Song; Minghui Dong; Fei Chen; Yajie Hu; Yongliang Zhu; Junrong Gu; Peifeng Chen; Yulin Xie; Caiyong Yuan; Zhongying Qiao; Yajie Yu; Penghui Cao; et al. (International Journal of Plant Production, 2024)

Prenatal exposure to poly/perfluoroalkyl substances and risk for congenital heart disease in offspring - Sainan Li; Chengrong Wang; Chen Yang; Yongyan Chen; Qianhui Cheng; Jufen Liu; Yali Zhang; Lei Jin; Zhiwen Li; Aiguo Ren; Linlin Wang (Journal of Hazardous Materials, 2024)

Adsorption-desorption of 241Am(Ⅲ) on montmorillonite colloids and quartz sand: Effects of pH, ionic strength, colloid concentration and grain size - Linlin Zhang; Ling Li; Ke Chen; Qiulan Zhang; Jingli Shao; Yali Cui; Jun Zhu; Aiming Zhang; Song Yang (Journal of Environmental Radioactivity, 2024)

Factors influencing marine ecological environment governance toward sustainability: a case study of Zhejiang Province - Linlin Chen; Yuejun He; Yuze He (Frontiers in Marine Science, 2024)
At present, the marine ecological environment is facing enormous pressure from human activities, and there is an urgent need for coordinated governance by multiple entities to ensure that the marine ecological environment can continuously meet the needs of sustainable development. Marine ecological environmental governance plays multiple roles in the sustainable development of the ocean characteristics. Most existing studies have explored this field from the perspective of the government and public, while failing to adequately account for the factors influencing enterprises’ participation in marine ecological environmental governance. This paper is an effort to provide some empirical research on the influencing factors of enterprises’ participation in marine ecological environmental governance. Based on existing literature, empirical research (213 middle managers were surveyed from 68 coastal enterprises in Zhejiang, China), this study extracts eight core factors that influence corporate participation in marine ecosystems and uses the Fuzzy Decision-making Trial and Evaluation Laboratory approach (Fuzzy DEMATEL). Furthermore, experts from Chinese backgrounds elucidated the complex interdependencies among the factors, based on which key influencing factors were identified. The empirical results indicate that government attention and support, legal and regulatory requirements, and cost-benefit accounting have a positive net effect on corporate participation in marine ecosystem management; when these factors are improved, they drive improvements in other factors(Corporate Capital Capability, Corporate Social Responsibility, Government Enforcement and Appraisal, The Attention of Corporate Leaders, Corporate Internal Management System). Additionally, interviews with Chinese business people support the robustness of the findings and suggest that policymakers cannot ignore government enforcement and assessment efforts. Overall, the study findings can help advance corporate participation in marine environmental governance.

Magnetite alleviating calcification of anaerobic granular sludge (AnGS): Electron transfer enhancement and ion competition - Linlin Chen; Ruoxuan Yuan; Xiangyang Xu; Liang Zhu (Science of The Total Environment, 2024)

Dominant contribution of combustion-related ammonium during haze pollution in Beijing - Libin Wu; Peng Wang; Qiang Zhang; Hong Ren; Zongbo Shi; Wei Hu; Jing Chen; Qiaorong Xie; Linjie Li; Siyao Yue; Lianfang Wei; Linlin Song; et al. (Science Bulletin, 2024)

Experimental investigation of propeller blade back cavitation induced pressure pulses by synchronous observation - Rui Wu; Heng Liu; Weiqi Chen; Sheng Ji; Linlin Cao; Dazhuan Wu (Ocean Engineering, 2024)

Evolution behavior of volatile components of shiitake mushrooms during infrared-assisted spouted bed drying - Yiming Xu; Wenchao Liu; Linlin Li; Weiwei Cao; Guangyue Ren; Houdong Shi; Yike Zhao; Junliang Chen; Xu Duan (Food Control, 2024)

Melatonin alleviates di-butyl phthalate (DBP)-induced ferroptosis of mouse leydig cells via inhibiting Sp2/VDAC2 signals - Si Yang; Meiwei Chen; Jiahui Meng; Chaoju Hao; Linlin Xu; Jinglei Wang; Jiaxiang Chen (Environmental Research, 2024)

Clinical Application of Polygenic Risk Score in IgA Nephropathy - Linlin Xu; Ting Gan; Pei Chen; Yang Liu; Shu Qu; Sufang Shi; Lijun Liu; Xujie Zhou; Jicheng Lv; Hong Zhang (Phenomics, 2024)

In Utero Exposure to Lead is Associated with Neural Tube Defects via Disturbing the Expression of Endocannabinoid Retrograde Signaling-Related Genes - Tian Tian; Huijun Dong; Shengju Yin; Mengyuan Liu; Yongyan Chen; Kuanhui Xiang; Linlin Wang; Jie Qiao; Aiguo Ren (Exposure and Health, 2024)

Recent advances in enhanced technology of Cr(VI) bioreduction in aqueous condition: A review - Linlin Ma; Nan Chen; Chuanping Feng; Qing Yang (Chemosphere, 2024)

Influence paradigms of soil moisture on land surface energy partitioning under different climatic conditions - Xiao Chen; Zhihua Pan; Binxiang Huang; Ju Liang; Jialin Wang; Ziyuan Zhang; Kang Jiang; Na Huang; Guolin Han; Buju Long; Zhenzhen Zhang; Jingyu Men; et al. (Science of The Total Environment, 2024)

Kinetics and debromination studies on the pyrolysis of waste printed circuit boards with the addition of copper and copper oxides - Tao Chen; Chuan Ma; Ben Wang; Linlin Xu; Wu Yang; Lushi Sun (Journal of Cleaner Production, 2024)

UV-B application during the aeration process improves the aroma characteristics of oolong tea - Xiaohui Wang; Jingjie Cao; Xin Cheng; Xuyang Liu; Wenfeng Zhu; Yan Li; Xiaochun Wan; Shengkeng Chen; Linlin Liu (Food Chemistry, 2024)

A novel baking additive: Preparation, characterization, and application of chitosan hydrochloride/carboxymethyl starch sodium nano-gel for wheat bread - Xinlai Dou; Yanling Hao; Ying Sun; Pin Yang; Linlin Liu; Yinyuan He; Yanguo Shi; Chunhua Yang; Fenglian Chen (Food Hydrocolloids, 2024)

Selective extraction of lithium ions by phosphoroxy-functionalized ionogels from the mother liquor of Li2CO3 - Yuhong Huang; Xiaowei Li; Guiling Luo; Duanjian Tao; Linlin Chen; Jing Sun; Bizuneh Kaleab; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2024)

Photocatalytic chitosan-based bactericidal films incorporated with WO3/AgBr/Ag and activated carbon for ethylene removal and application to banana preservation - Feng Xiao; Yewen Xiao; Wei Ji; Linlin Li; Yimeng Zhang; Minmin Chen; Hualin Wang (Carbohydrate Polymers, 2024)

Geomorphic adjustments of channel bars in the braided reach of the lower Yellow river from 1986 to 2018 - Jie Li; Junqiang Xia; Lingzhong Kong; Qingfeng Ji; Linlin Li; Fan chen (CATENA, 2024)

Distribution and influencing factors of macrobenthos on three seagrass beds in the intertidal zone of Shandong province, China - Yinglu Ji; Bo Song; Jiangling Xu; Shaoyu Jiang; Linlin Chen; Baoquan Li (Frontiers in Marine Science, 2024)
Introduction The macrobenthos plays a vital role within the ecosystem of seagrass beds, with its characteristics and spatial distribution serving as indicators of the well-being of the seagrass beds. Methods In August 2018, three seagrass beds located in the Yellow River Estuary of Dongying, the west coast of Yantai, and Swan Lake of Weihai, were investigated to compare the ecological influences of seagrass habitat on the benthic environment and macrobenthic community. Within each seagrass bed, porewater, sediment, and macrobenthos were sampled from three separate stations (center of seagrass bed, edge of seagrass bed and bare area). Results and discussion One-way ANOVA showed significant differences ( p < 0.05) in environmental factors and macrobenthos species, abundance, biomass and diversity indices among the three seagrass beds. The present data did not show significant impacts on habitat and macrobenthos in the different coverage areas of seagrass beds at the investigated spatial scales, though crustacea and some carnivores were relatively more inclined to inhabit areas with higher seagrass densities. Aquaculture and eutrophication may trigger the loss of seagrass bed habitats, that affects macrobenthic biodiversity, and conservation measures are needed to protect seagrass bed habitats.

N-methyl pyrrolidone manufacturing wastewater as the electron donor for denitrification: From bench to pilot scale - Songyun Chen; Xiaohui Zhu; Ge Zhu; Bin Liang; Jin Luo; Danyang Zhu; Linlin Chen; Yongming Zhang; Bruce E. Rittmann (Science of The Total Environment, 2024)

The pollution of airborne ARGs and microorganisms during wastewater treatment process and their UV mediated removal mechanism - Yanjie Wang; Hao Chen; Liying Yang; Song Zhang; Kai Yang; Linlin Hua (Journal of Water Process Engineering, 2024)

Multi-sensor integrated mapping of global XCO2 from 2015 to 2021 with a local random forest model - Jiabin Chen; Ruohua Hu; Leyan Chen; Zihao Liao; Linlin Che; Tongwen Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Effects of chitosan and its oligosaccharide on gut microbiota and metabolites disturbed by excessive protein consumption in vivo and in vitro - Linlin Wang; Lilong Wang; Nan Wang; Chen Song; Chengrong Wen; Shuang Song (Food Bioscience, 2024)

Comparative transcriptome analysis of hybrid Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) and Epinephelus fuscoguttatus under temperature stress - Pengfei Duan; Yongsheng Tian; Zhentong Li; Shuai Chen; Linlin Li; Xinyi Wang; Linna Wang; Yang Liu; Jieming Zhai; Wensheng Li; Qingbin Wang; Wenhui Ma; et al. (Aquaculture, 2024)

Duck Tembusu virus infection activates the MKK3/6-p38 MAPK signaling pathway to promote virus replication - Yuting Cheng; Linlin Jiao; Jinying Chen; Peiyao Chen; Fang Zhou; Jilin Zhang; Mixue Wang; Qingguo Wu; Shinuo Cao; Huipeng Lu; Zhi Wu; Anping Wang; et al. (Veterinary Microbiology, 2024)

Integrating photovoltaic noise barriers and electric vehicle charging stations for sustainable city transportation - Kai Zhang; Min Chen; Rui Zhu; Fan Zhang; Teng Zhong; Jian Lin; Linlin You; Guonian Lü; Jinyue Yan (Sustainable Cities and Society, 2024)

Heat stress reduces brown adipose tissue activity by exacerbating mitochondrial damage in type 2 diabetic mice - Penghua Lai; Linlin Zhang; Yan Qiu; Jie Ren; Xue Sun; Ting Zhang; Liuyi Wang; Sijie Cheng; Sijia Liu; Hongli Zhuang; Daiwei Lu; Shaoliang Zhang; et al. (Journal of Thermal Biology, 2024)

Influence of sampling location and processing on the assembly and network of Polygoni Multiflori Radix surface microbiome - Guangfei Wei; Yichuan Liang; Guozhuang Zhang; Zhaoyu Zhang; Yongqing Zhang; Shilin Chen; Linlin Dong (International Journal of Food Microbiology, 2024)

Acid-assisted ultrasonic preparation of nitrogen-doped MXene quantum dots for the efficient fluorescence “off-on-off” detection of Zn(II) in water and oxalic acid in vegetables - Jinwen Yang; Linlin Chen; Jie Qi; Feili Luo; Lin Li; Honghong Wu; Feifei Cao; Jiangjiang Gu (Food Chemistry, 2024)

Performance and mechanism of Al, N co-doped carbon/nano-TiO2 photocatalytic oxidation for the removal of ammonia nitrogen and Ni/Co complexes from ternary precursor wastewater - Peize Li; Yaoguo Huang; Yali Zhang; Linlin Chen (Chemical Engineering Journal, 2024)

Angiotensin II type 2 receptor agonist attenuates LPS-induced acute lung injury through modulating THP-1-derived macrophage reprogramming - Liangzhi Chen; Ping Gong; Yue Su; Linlin Meng; Muyun Wang; Wei Gao; Qinghua Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

S doped g-C3N5 for highly efficient photocatalytic H2O2 production and PPCPs degradation via directional transfer of electrons - Wenjuan Wang; Nan Zhou; Yakun Li; Zhengqiaoruo Zhu; Xiguo Chen; Linlin Zhang (Journal of Environmental Chemical Engineering, 2023)

Stable precipitation isotope records of cold wave events in Eurasia - Xinrui Lin; Guofeng Zhu; Dongdong Qiu; Linlin Ye; Yuwei Liu; Longhu Chen; Jiawei Liu; Siyu Lu; Lei Wang; Kailiang Zhao; Wenhao Zhang; Rui Li; et al. (Atmospheric Research, 2023)

circ_SPEF2 Regulates the Balance of Treg Cells by Regulating miR-16-5p/BACH2 in Lymphoma and Participates in the Immune Response - Jie Zhou; Min Xu; ZhaoZhao Chen; LinLin Huang; ZhuoLin Wu; ZhongPei Huang; Lin Liu (Tissue Engineering and Regenerative Medicine, 2023)

Establishment of ultrasensitive immunoassay strip based on colloidal gold-McAb probe for detecting cyproheptadine hydrochloride and six phenothiazines in feed - Xiaofei Hu; Guanqiong Na; Yaning Sun; Yunrui Xing; Linlin Chen; Zhang Gaiping (Food Additives & Contaminants: Part A, 2023)

Insight into the mechanisms of neuroendocrine toxicity induced by 6:2FTCA via thyroid hormone disruption - Linlin Wu; Jie Gu; Xinjie Duan; Feng Ge; Heyong Ye; Lingcan Kong; Wenwei Liu; Rong Gao; Jiandong Jiao; Huanhuan Chen; Guixiang Ji (Chemosphere, 2023)

Spatio-temporal distribution of macrobenthos and benthic ecological health status in the Bohai Sea and the northern Yellow Sea, China - Shaoyu Jiang; Wenzheng Fan; Linlin Chen; Jing Chen; Baoquan Li (Marine Pollution Bulletin, 2023)

Structural and gelling properties of whey proteins influenced by various acids: Experimental and computational approaches - Linlin Zhang; Zhuo Zhang; Stephen R. Euston; Bo Li; Erhu Li; Caixia Fu; Guodong Chen (Food Hydrocolloids, 2023)

Biomineralization of uranium by Desulfovibrio desulfuricans A3-21ZLL under various hydrochemical conditions - Bei Zhao; Xin Chen; Hongliang Chen; Linlin Zhang; Jiang Li; Yadan Guo; Haiyan Liu; Zhongkui Zhou; Pingchao Ke; Zhanxue Sun (Environmental Research, 2023)

A review of adsorption materials and their application of 3D printing technology in the separation process - Jiangtao Yu; Jie Zhu; Linlin Chen; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Chemical Engineering Journal, 2023)

Depth investigation of the regulation mechanism of SiO2 on the denitrification performance and sulfur resistance of MnCe/Ti SCR catalyst - Mengxia Qing; Linlin Zhang; Liang Liu; Yaxin Chen; Yunda Su; Sheng Su; Song Hu; Yi Wang; Jun Xiang (Chemical Engineering Journal, 2023)

Frequency specific alterations of the degree centrality in patients with acute basal ganglia ischemic stroke: a resting-state fMRI study - Hao Chen; Linlin Zhan; Qianqian Li; Chaoguo Meng; Xuemei Quan; Xiaoling Chen; Zeqi Hao; Jing Li; Yanyan Gao; Huayun Li; Xize Jia; Mengting Li; et al. (Brain Imaging and Behavior, 2023)
This study intended to investigate the frequency specific brain oscillation activity in patients with acute basal ganglia ischemic stroke (BGIS) by using the degree centrality (DC) method. A total of 34 acute BGIS patients and 44 healthy controls (HCs) underwent resting-state functional magnetic resonance imaging (rs-fMRI) scanning. The DC values in three frequency bands (conventional band: 0.01–0.08 Hz, slow‑4 band: 0.027–0.073 Hz, slow‑5 band: 0.01–0.027 Hz) were calculated. A two-sample t -test was used to explore the between-group differences in the conventional frequency band. A two-way repeated-measures analysis of variance (ANOVA) was used to analyze the DC differences between groups (BGIS patients, HCs) and bands (slow‑4, slow‑5). Moreover, correlations between DC values and clinical indicators were performed. In conventional band, the DC value in the right middle temporal gyrus was decreased in BGIS patients compared with HCs. Significant differences of DC were observed between the two bands mainly in the bilateral cortical brain regions. Compared with the HCs, the BGIS patients showed increased DC in the right superior temporal gyrus and the left precuneus, but decreased mainly in the right inferior temporal gyrus, right inferior occipital gyrus, right precentral, and right supplementary motor area. Furthermore, the decreased DC in the right rolandic operculum in slow-4 band and the right superior temporal gyrus in slow-5 band were found by post hoc two-sample t -test of main effect of group. There was no significant correlation between DC values and clinical scales after Bonferroni correction. Our findings showed that the DC changes in BGIS patients were frequency specific. Functional abnormalities in local brain regions may help us to understand the underlying pathogenesis mechanism of brain functional reorganization of BGIS patients.

A quantitative analysis of the impact of reclamation on the stability of coastal wetlands - Yanhui Chen; Linlin Cui; Guosheng Li; Jiping Liu; Lijuan Li; Dandan Zhao (Ocean & Coastal Management, 2023)

Solar forcing and ENSO regulated rates of change of ecosystems in Northeast China since the last deglaciation - Guizai Gao; Honghao Niu; Lina Song; Jiangyong Wang; Meng Meng; Zhuo Yang; Linlin Liu; Yuanxiang Wei; Niankang Chen; Jihuai Yu; Dongmei Jie (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Coupling isotopic signatures and partial extraction method to examine lead pollution in mangrove sediments - Zhenghua Tao; Jian Hu; Qingjun Guo; Rongfei Wei; Linlin Jiao; Yanping Li; Fengyuan Chen; Bailing Fan; Wenlu Lan; Ke Pan (Journal of Hazardous Materials, 2023)

An ultra-stable high entropy metal nitride for aerobic oxidative desulfurization and source recovery of aromatic sulfides from fuel oils - Peiwen Wu; Chang Deng; Penghui Liu; Feng Liu; Linlin Chen; Bangzhu Wang; Wenshuai Zhu; Chunming Xu (Chemical Engineering Journal, 2023)

Contrasting effects of rice husk and its biochar on N2O emissions and nitrogen leaching from Lei bamboo soils under subtropical conditions - Rong Zhou; Zhe Chen; Ali EI-Naggar; Linlin Tian; Chengpeng Huang; Zhen Zhang; Kumuduni Niroshika Palansooriya; Yongfu Li; Bing Yu; Scott X. Chang; Yanjiang Cai (Biology and Fertility of Soils, 2023)

Evaluation and analysis of green efficiency of China's coastal ports under the "double carbon" goal: two improved DEA models with CO2 emissions - Linlin Cui; Long Chen; Xiao Yang (Environment, Development and Sustainability, 2023)

Quadristerols A−G: Seven undescribed ergosterols from Aspergillus quadrilineata - Mengsha Wei; Xiaoxin Li; Hong Liao; Linlin Liu; Qin Li; Weiguang Sun; Chunmei Chen; Hucheng Zhu; Yonghui Zhang (Phytochemistry, 2023)

Occurrence of fungi and mycotoxins in herbal medicines and rapid detection of toxin-producing fungi - Guangfei Wei; Xiaotong Guo; Yichuan Liang; Congsheng Liu; Guozhuang Zhang; Conglian Liang; Zhixin Huang; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Pollution, 2023)

Effect of non-permeable cryoprotectant sucrose on the development of spotted knifejaw (Oplegnathus punctatus) embryos - Linlin Li; Yongsheng Tian; Zhentong Li; Pengfei Duan; Xinyi Wang; Shuai Chen; Linna Wang; Yang Liu; Qingbin Wang; Wensheng Li; Xia Zhao; Wenhui Ma; et al. (Cryobiology, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Inequality and its driving forces in residential CO2 emission: Perspective of energy use pattern - Lei Chen; Linyu Xu; Yongyang Wang; Linlin Xia; Zhifeng Yang (Journal of Cleaner Production, 2023)

Molecular mechanisms affecting the stability of high internal phase emulsions of zein-soy isoflavone complexes fabricated with ultrasound-assisted dynamic high-pressure microfluidization - Junrong Huang; Xutao Chen; Danxia Su; Linlin Chen; Caidi Chen; Bei Jin (Food Research International, 2023)

The lysosome-phagosome pathway mediates immune regulatory mechanisms in Mesocentrotus nudus against Vibrio coralliilyticus infection - Yanxia Wang; Quanchao Wang; Linlin Chen; Baoquan Li (Fish & Shellfish Immunology, 2023)

3D-printed titanium-based ionic sieve monolithic adsorbent for selective lithium recovery from salt lakes - Jiangtao Yu; Jie Zhu; Guiling Luo; Linlin Chen; Xiaowei Li; Peng Cui; Peiwen Wu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Desalination, 2023)

Pathogenicity and immune response of the sea urchin Mesocentrotus nudus to Vibrio coralliilyticus infection - Yanxia Wang; Quanchao Wang; Linlin Chen; Ruxin Ding; Zirui Peng; Baoquan Li (Aquaculture, 2023)

Distinct functions of TIR1 and AFB1 receptors in auxin signaling - Huihuang Chen; Lanxin Li; Minxia Zou; Linlin Qi; Jiří Friml (Molecular Plant, 2023)

Biochar accelerates the start-up of the anammox process: Phenomenon and potential mechanisms - Hui Chen; Shenbo Cao; Linlin Chen; Zhicheng Zhang; Juesheng Tian; Rencun Jin; Jun Yao (Journal of Water Process Engineering, 2023)

Dissipation and movement of soil water in artificial forest in arid oasis areas: Cognition based on stable isotopes - Dongdong Qiu; Guofeng Zhu; Xinrui Lin; Yinying Jiao; Siyu Lu; Jiatong Liu; Jiawei Liu; Wenhao Zhang; Linlin Ye; Rui Li; Qinqin Wang; Longhu Chen (CATENA, 2023)

The effect of SARS-CoV-2 infection on human embryo early development: a multicenter prospective cohort study - Xiaolei Chen; Huangcong Shi; Cheng Li; Wanxia Zhong; Linlin Cui; Wenjun Zhang; Ling Geng; Kuona Hu; Mei Fang; Daimin Wei; Junhao Yan; Yun Sun; et al. (Science China Life Sciences, 2023)

Genetic diversity and population structure of the sea star Asterias amurensis in the northern coast of China - Quanchao Wang; Ying Liu; Zirui Peng; Linlin Chen; Baoquan Li (Journal of Oceanology and Limnology, 2023)

Hair Selenium of Residents in Keshan Disease Endemic and Non-endemic Regions in China - Yuehui Jia; Ruixiang Wang; Guijin Li; Chen Feng; Lei Qi; Yuanyuan Wang; Shengqi Su; Yuanjie Zou; Xu Liu; Yanan Wang; Yiyi Zhang; Linlin Du; et al. (Biological Trace Element Research, 2023)

Estimation of urban-scale photovoltaic potential: A deep learning-based approach for constructing three-dimensional building models from optical remote sensing imagery - Longxu Yan; Rui Zhu; Mei-Po Kwan; Wei Luo; De Wang; Shangwu Zhang; Man Sing Wong; Linlin You; Bisheng Yang; Biyu Chen; Ling Feng (Sustainable Cities and Society, 2023)

Glyphosate induces autophagy in hepatic L8824 cell line through NO-mediated activation of RAS/RAF/MEK/ERK signaling pathway and energy metabolism disorders - Linlin Zhang; Lu Chen; Meng Qi; Fuchang Yu; Xiaotong Ni; Haozheng Hong; Haotian Xu; Shiwen Xu (Fish & Shellfish Immunology, 2023)

Cloning and expression of the mitochondrial cytochrome c oxidase subunit II gene in Sitophilus zeamais and interaction mechanism with allyl isothiocyanate - Linlin Jiang; Yue Li; Weilin Shi; Wei Chen; Zhiqing Ma; Juntao Feng; Ahmed S. Hashem; Hua Wu (Pesticide Biochemistry and Physiology, 2023)

Real-time monitoring of mercury(II) in water and food samples using a quinoline-based ionic probe - Siying Che; Linlin Yin; Ming Chen; Yao Fan; Anni Xu; Chunsong Zhou; Haiyan Fu; Yuanbin She (Food Chemistry, 2023)

Allosteric synthetic antibody (Allo-SyAb) for improved cancer immunotherapy - Jiajing Chen; Mengchen Xu; Yongxin Zhang; Linlin Xu; Shuyue Zhao; Yingli An; Rujiang Ma; Yang Liu; Feihe Ma; Linqi Shi (Chemical Engineering Journal, 2023)

Nanophytoplankton and microphytoplankton in the western tropical Pacific Ocean: its community structure, cell size and carbon biomass - Wenzhuo Yan; Zhuo Chen; Linlin Zhang; Feng Wang; Guicheng Zhang; Jun Sun (Frontiers in Marine Science, 2023)
Phytoplankton, as a crucial component of the marine ecosystem, plays a fundamental role in global biogeochemical cycles. This study investigated the composition and distribution of phytoplankton in the western Tropical Pacific Ocean using the Utermöhl method and carbon volume conversion. We identified four primary groups of phytoplankton: dinoflagellates (181 species), diatoms (73 species), cyanobacteria (4 species), and chrysophyceae (2 species). The clustering analysis classified phytoplankton into four groups based on their composition, which were found to be closely related to ocean currents. Diatoms were highly abundant in areas influenced by current-seamount interaction. In contrast, areas with little influence from ocean currents were dominated by Trichodesmium . The majority of phytoplankton had an equivalent spherical diameter (ESD) of 2-12 μm, with a few exceeding 25 μm. Although nanophytoplankton (ESD = 2-20 µm) dominated cell abundance, microphytoplankton (ESD = 20-200 µm) contributed significantly to carbon biomass (792.295 mg m -3 ). This study yielded valuable insights into the distribution and composition of phytoplankton in the western tropical Pacific Ocean, shedding light on the relationship between species distribution and ocean currents. In addition, it provided fundamental information regarding cell size and carbon biomass within the region.

Singlet oxygen generation in light-assisted peroxymonosulfate activation by carbon nitride: Role of elevated crystallinity - Beizhao Chen; Xun Liu; Bei Liu; Qi Han; Li Li; Li Wang; Yufei Shu; Linlin Zang; Wenlei Zhu; Zhongying Wang (Chemosphere, 2023)

Mineralogical characteristics and recovery process optimization analysis of a refractory gold ore with gold particles mainly encapsulated in pyrite and Arsenopyrite - Jiafeng Li; Hongying Yang; Rongxin Zhao; Linlin Tong; Qiao Chen (Geochemistry, 2023)

Tannin alleviates glyphosate exposure-induced apoptosis, necrosis and immune dysfunction in hepatic L8824 cell line by inhibiting ROS/PTEN/PI3K/AKT pathway - Linlin Zhang; Lu Chen; Dayong Tao; Fuchang Yu; Meng Qi; Shiwen Xu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

MOF-templated fabrication of Ni@C/g-C3N4 catalyst with high-dense accessible active sites achieving dicyclopentadiene hydrogenation at ambient conditions and comprehensive mechanism insight - Chenghong Wu; Xiaopeng Chen; Jiezhen Liang; Jiawei Fu; Zhongyao Zhang; Xiaojie Wei; Linlin Wang (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Long-term non-phosphorus application increased paddy methane emission by promoting organic acid and methanogen abundance in Tai Lake region, China - Chen Xu; Susu Shen; Beibei Zhou; Yuanyuan Feng; Zhu He; Linlin Shi; Yu Wang; Haihou Wang; Tripti Mishra; Lihong Xue (Science of The Total Environment, 2023)

Relationships between denitrification rates and functional gene abundance in a wetland: The roles of single- and multiple-species plant communities - Yushuang Kong; Haikuo Zhang; Linlin Tian; Junji Yuan; Youchao Chen; Yan Li; Jian Chen; Scott X. Chang; Yunying Fang; Ehsan Tavakkoli; Yanjiang Cai (Science of The Total Environment, 2023)

Enhanced antihypertensive potential of fermented pomegranate juice: The contribution of phenolic compounds biotransformation and the resultant angiotensin-I-converting enzyme inhibition mechanism - Li Chen; Linlin Wang; Guowei Shu; Jiaojiao Yuan; Jiying Zhang; Shan Qin; Jianke Li (Food Chemistry, 2023)

Preparation of PLGA/ε-polylysine nanofibers and their application for pork preservation - Minmin Chen; Linlin Li; Li Xia; Yaqiong Kong; Suwei Jiang; Xiaoju Chen; Hualin Wang (Food Packaging and Shelf Life, 2023)

Selective recovery of lithium from spent LiFePO4 battery via a self-catalytic air oxidation method - Hao Jin; Jialiang Zhang; Cheng Yang; Linlin Ma; Yongqiang Chen; Chengyan Wang (Chemical Engineering Journal, 2023)

Upscaling of Se(IV) sorption coefficients with hierarchical mineral characterization in multi-scale fractured granite - Funing Ma; Xiaoying Zhang; Chuanjun Zhan; Wei Chen; Linlin Qi; Zhenxue Dai (Stochastic Environmental Research and Risk Assessment, 2023)

Phthalate Mixture Exposure is Associated with Elevated Blood Pressure in Chinese Children: A Panel Study - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Meng Li; Shuang Chen; Jie Yu; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Exposure and Health, 2023)

Crop type mapping in the central part of the North China Plain using Sentinel-2 time series and machine learning - Ke Luo; Linlin Lu; Yanhua Xie; Fang Chen; Fang Yin; Qingting Li (Computers and Electronics in Agriculture, 2023)

Air pollution exposure and ovarian reserve impairment in Shandong province, China: The effects of particulate matter size and exposure window - Lihong Pang; Wenhao Yu; Jiale Lv; Yunde Dou; Han Zhao; Shanshan Li; Yuming Guo; Gongbo Chen; Linlin Cui; Jingmei Hu; Yueran Zhao; Qi Zhao; et al. (Environmental Research, 2023)

Convolutional neural networks (CNNs)-based multi-category damage detection and recognition of high-speed rail (HSR) reinforced concrete (RC) bridges using test images - Lingkun Chen; Wenxin Chen; Lu Wang; Chencheng Zhai; Xiaolun Hu; Linlin Sun; Yuan Tian; Xiaoming Huang; Lizhong Jiang (Engineering Structures, 2023)

Electrochemical lithium ion pumps for lithium recovery: A systematic review and influencing factors analysis - Guiling Luo; Xiaowei Li; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Desalination, 2023)

Multi-scale ocean dynamical processes in the Indo-Pacific Convergence Zone and their climatic and ecological effects - Yan Du; Fan Wang; Tianyu Wang; Weiwei Liu; Linlin Liang; Ying Zhang; Yunfan Chen; Jiaxing Liu; Wei Wu; Kefu Yu; Jing Zhang (Earth-Science Reviews, 2023)

Preparation of high hydrophilic H2TiO3 ion sieve for lithium recovery from liquid lithium resources - Jing Sun; Xiaowei Li; Yuhong Huang; Guiling Luo; Duanjian Tao; Jiangtao Yu; Linlin Chen; Yanhong Chao; Wenshuai Zhu (Chemical Engineering Journal, 2023)

Metagenomic and extracellular polymeric substances analysis reveals the mechanism of exogenous N-hexanoyl-L-homoserine lactone in alleviating the inhibition of perfluorooctanoic acid on anammox process - Linqin Tang; Chengyuan Su; Cuiping Fan; Linlin Cao; Zhu Liang; Yufeng Xu; Zhengpeng Chen; Qing Wang; Menglin Chen (Bioresource Technology, 2023)

Short telomeres impede germ cell specification by upregulating MAPK and TGFβ signaling - Chenglei Tian; Dai Heng; Nannan Zhao; Linlin Liu; Xiaoyan Sheng; Jiyu Chen; Lin Liu (Science China Life Sciences, 2023)

Cenozoic plants from Tibet: An extraordinary decade of discovery, understanding and implications - Zhekun Zhou; Jia Liu; Linlin Chen; Robert A. Spicer; Shufeng Li; Jian Huang; Shitao Zhang; Yongjiang Huang; Linbo Jia; Jinjin Hu; Tao Su (Science China Earth Sciences, 2023)

Chinese consensus guidelines for therapeutic drug monitoring of polymyxin B, endorsed by the Infection and Chemotherapy Committee of the Shanghai Medical Association and the Therapeutic Drug Monitoring Committee of the Chinese Pharmacological Society - Xiaofen Liu; Chenrong Huang; Phillip J. Bergen; Jian Li; Jingjing Zhang; Yijian Chen; Yongchuan Chen; Beining Guo; Fupin Hu; Jinfang Hu; Linlin Hu; Xin Li; et al. (Journal of Zhejiang University-SCIENCE B, 2023)

Otus scops adenovirus: the complete genome sequence of a novel aviadenovirus discovered in a wild owl - Weibo Zheng; Tingshu Jiang; Zhe Zhang; Dong Pan; Wenli Tang; Youzhi Li; Linlin Jiang; Hongwei Zhu; Xin Yu; Guozhong Chen; Jiao Wang; Jianlong Zhang; et al. (Archives of Virology, 2023)

The Environmental Niche of the Tuna Purse Seine Fleet in the Western and Central Pacific Ocean Based on Different Fisheries Data - Shenglong Yang; Linlin Yu; Fei Wang; Tianfei Chen; Yingjie Fei; Shengmao Zhang; Wei Fan (Fishes, 2023)
Understanding the spatial pattern of human fishing activity is very important for fisheries resource monitoring and spatial management. The environmental preferences of tropical tuna purse seine fleet in the Western and Central Pacific Ocean (WCPO) were constructed and compared at different spatial scales based on the fishing effort (FE) data from the available automatic identification system (AIS) and commercial fishery data compiled from the Western and Central Pacific Fisheries Commission (WCPFC), using maximum entropy (MaxEnt) methods. The MaxEnt models were fitted with FE and commercial fishery data and remote sensing environmental data. Our results showed that the area under the curve (AUC) value each month based on the commercial fishery data (1°) and FE at 0.25° and 0.5° spatial scales was greater than 0.8. The AUC values each month based on the FE data at a 1° scale ranged from 0.775 to 0.829. The AUC values based on commercial fishing data at the 1° scale were comparable to the model results based on FE data at the 0.5° scale and inferior to the model results based on FE data at the 0.25° scales. Overall, the sea surface temperature (SST), temperature at 100 metres (T100), oxygen concentration at 100 metres (O100) and total primary production (PP) had the greatest influence on the distribution of the purse seine tuna fleet. The oxygen concentration at 200 metres (O200), distance to shore (DSH), dissolved oxygen (Dox), EKE, mixed layer depth (Mld), sea surface salinity (SSS), salinity at 100 metres (S100) and salinity at 200 metres (S200) had moderate influences, and other environmental variables had little influence. The suitable habitat areas varied in response to environmental conditions. The purse seine tuna fleet was mostly present at locations where the SST, T100, O100, O200 and PP were 28–30 °C, 27–29 °C, 150–200 mmol/m3 and 5–10 mg/m−3, respectively. The MaxEnt models enable the integration of AIS data and high-resolution environmental data from satellite remote sensing to describe the spatiotemporal distribution of the tuna purse seine fishery and the influence of environmental variables on the distribution, and can provide forecasts for fishing ground distributions based on future remote sensing environmental data.

Heterosis in growth and low temperature tolerance in Jinhu grouper (Epinephelus fuscoguttatus ♀ × Epinephelus tukula ♂) - Shuai Chen; Yongsheng Tian; Zhentong Li; Yang Liu; Ziqi Li; Pengfei Duan; Linlin Li; Xinyi Wang; Linna Wang; Xinlei He; Xia Zhao; Wensheng Li; et al. (Aquaculture, 2023)

Current recycling strategies and high-value utilization of waste cotton - Linlin Lu; Wei Fan; Xue Meng; Lili Xue; Shengbo Ge; Chen Wang; Shin Ying Foong; Cindy S.Y. Tan; Christian Sonne; Mortaza Aghbashlo; Meisam Tabatabaei; Su Shiung Lam (Science of The Total Environment, 2023)

Different nitrogen fertilizer application in the field affects the morphology and structure of protein and starch in rice during cooking - Shijie Shi; Gaoyu Zhang; Linlin Chen; Wenhui Zhang; Xiaodong Wang; Keqiang Pan; Lina Li; Jing Wang; Juan Liu; Cougui Cao; Yang Jiang (Food Research International, 2023)

Island-like CeO2 decorated LiMn2O4: Surface modification enhancing electrochemical lithium extraction and cycle performance - Guiling Luo; Xiaowei Li; Linlin Chen; Yuning Zhang; Jun Gu; Yanhong Chao; Wenshuai Zhu; Zhichang Liu; Chunming Xu (Chemical Engineering Journal, 2023)

Combining microclimatic monitoring with questionnaires, for understanding thermal comfort in Linpan, a typical agricultural ecosystem settlement in the Chengdu plain - Linlin Chen; Gretchen Kalonji; Lilai Xu; Pufan Ma; Linmiao Hu (Building and Environment, 2023)

TRIM11, a new target of p53, facilitates the migration and invasion of nasopharyngeal carcinoma cells - Ziyi Zhao; Jinkuang Deng; Ming Lu; Jun Yang; Linlin Chen; DianYuan Li; Yi Sang (Molecular Biology Reports, 2023)
Background Although tripartite motif-containing protein 11 (TRIM11) is known to be associated with a variety of cancers, its role in nasopharyngeal carcinoma (NPC) is unclear. Methods and results To investigate the role of TRIM11 in NPC, TRIM11 was stably overexpressed in 6–10B and CNE2 cells with lentiviral vectors and knocked down in S18 and 5–8F cells using the CRISPR/Cas9 system. Transwell assays and wound-healing assays revealed that TRIM11 facilitated the migration and invasion of NPC cells. Mechanistically, we found that p53 inhibits TRIM11 expression by binding to its promoter. Conclusions TRIM11 may serve as a potential diagnostic marker for NPC and has a certain therapeutic value.

High-quality chromosome-level genome assembly of Pacific cod, Gadus macrocephalus - Yiqing Ma; Yuan Li; Chen Jiang; Li Zheng; Shenghao Liu; Linlin Zhao (Frontiers in Marine Science, 2022)

Structural and functional analysis of a potent human neutralizing antibody against enterovirus A71 - Zhe Chen; Linlin Bao; Bin Zhu; Hua Fu; Shuangli Zhu; Tianjiao Ji; Ying Xue; Chuan Liu; Xurong Wang; Fengdi Li; Qi Lv; Feifei Qi; et al. (Science China Life Sciences, 2022)

Increased Expression of CD95 in CD4+ Effector Memory T Cells Promotes Th17 Response in Patients with Myasthenia Gravis - Xiaoyu Huang; Jie Zhu; Tan Liu; Fengzhan Li; Tingting Yang; Hao Li; Fei Chen; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; Deqin Geng (Journal of Neuroimmune Pharmacology, 2022)

Core rhizosphere microbiome of Panax notoginseng and its associations with belowground biomass and saponin contents - Guangfei Wei; Guozhuang Zhang; Mengzhi Li; Congsheng Liu; Fugang Wei; Yong Wang; Zhixin Huang; Zhongjian Chen; Yuqing Zheng; Shilin Chen; Linlin Dong (Environmental Microbiology, 2022)
The core rhizosphere microbiome is critical for plant fitness. However, its contribution to the belowground biomass and saponin contents of Panax notoginseng remains unclear. High‐throughput sequencing of amplicon and metagenome was performed to obtain the microbiome profiles and functional traits in P. notoginseng rhizosphere across a large spatial scale. We obtained 639 bacterial and 310 fungal core OTUs, which were mainly affected by soil pH and organic matter (OM). The core taxa were grouped into four ecological clusters (i.e. high pH, low pH, high OM and low OM) for sharing similar habitat preferences. Furthermore, structural equation modelling (SEM) and correlation analyses revealed that the diversity and composition of core microbiomes, as well as the metagenome‐derived microbial functions, were related to belowground biomass and saponin contents. Key microbial genera related to the two plant indicators were also identified. In short, this study explored the main driving environmental factors of core microbiomes in the P. notoginseng rhizosphere and revealed that the core microbiomes and microbial functions potentially contributed to the belowground biomass and saponin contents of the plant. This work may enhance our understanding of interactions between microbes and perennial plants and improve our ability to manage root microbiota for the sustainable production of herbal medicine.

Identification and functional analysis of two GJA8 variants in Chinese families with eye anomalies - Linlin Zhou; Xuejiao Sun; Xinyao Wang; Kangyu Liu; Zilin Zhong; Jianjun Chen (Molecular Genetics and Genomics, 2022)

Surveillance of long-term environmental elements and PM2.5 health risk assessment in Yangtze River Delta, China, from 2016 to 2020 - Keqin Wu; Yuanhua Meng; Yan Gong; Xuhui Zhang; Linlin Wu; Xinliang Ding; Xiaofeng Chen (Environmental Science and Pollution Research, 2022)

Associations of urinary polycyclic aromatic hydrocarbon metabolites and blood pressure with the mediating role of cytokines: A panel study among children - Miao Liu; Lei Zhao; Linlin Liu; Wenting Guo; Huihua Yang; Jie Yu; Shuang Chen; Meng Li; Qin Fang; Xuefeng Lai; Liangle Yang; Rui Zhu; et al. (Environmental Science and Pollution Research, 2022)

Taxonomic Composition and Spatial Distribution of Meiofauna Community from a Sandy Intertidal Zone in Sishili Bay, Yellow Sea Coast (Northern China) - Olga N. Pavlyuk; Yulia A. Trebukhova; Ilya A. Shcherbakov; Tatiana S. Tarasova; Konstantin A. Lutaenko; Linlin Chen; Bo Song; Xiaojing Li; Baoquan Li (Journal of Ocean University of China, 2022)

Identification and Characterization of the Homeobox Gene Family in Fusarium pseudograminearum Reveal Their Roles in Pathogenicity - Yuming Ma; Jingya Zhao; Wenbo Chen; Xuejing Geng; Tianli He; Shengli Ding; Bingjian Sun; Honglian Li; Linlin Chen (Biochemical Genetics, 2022)

The Structure and Function of Microbial Community in Rhizospheric Soil of American Ginseng (Panax quinquefolius L.) Changed with Planting Years - Guozhong Chen; Ying Xue; Xin Yu; Chongwei Li; Yuping Hou; Hongwei Zhu; Linlin Jiang; Weibo Zheng; Zhibin Feng; Youzhi Li; Wenli Tang; Xiaoyu Zhao; et al. (Current Microbiology, 2022)

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

AlgaeMask: An Instance Segmentation Network for Floating Algae Detection - Xiaoliang Wang; Lei Wang; Liangyu Chen; Feng Zhang; Kuo Chen; Zhiwei Zhang; Yibo Zou; Linlin Zhao (Journal of Marine Science and Engineering, 2022)
Video surveillance on the offshore booster station and around the coast is a effective way to monitor floating macroalgae. Previous studies on floating algae detection are mainly based on traditional image segmentation methods. However, these algorithms cannot effectively solve the problem of extracting Ulva prolifra and Sargassum at different sizes and views. Recently, instance segmentation methods have achieved great success in computer vision applications. In this paper, based on the CenterMask network, a novel instance segmentation architecture named AlgaeMask is proposed for floating algae detection from the surveillance videos. To address the feature extraction ability of the network in the inter-dependencies for position and channel, we introduce a new OSA-V3 module with the dual-attention block, which consists of a position attention mechanism and channel attention mechanism. Meanwhile, scale-equalizing pyramid convolution is introduced to solve the problem of scale difference. Finally, we introduce the feature decoder module based on FCOS head and segmentation head to obtain the segmentation area of floating algae in each bounding box. The extensive experiment results show that the average precision of our AlgaeMask in the tasks of mask segmentation and box detection can reach 44.22% and 48.13%, respectively, which has 15.09% and 8.24% improvement over CenterMask. In addition, the AlgaeMask can meet the real-time requirements of floating algae detection.

Radioactivity of Strontium-90 in Soil Samples Along the Hai River in Tianjin, China - Fei Chen; Linlin Yan; Qiang Xiong; Xiao Ge; Jing Liang; Zhen Zhang; Shengyuan Yang; Ling Jiao (Water, Air, & Soil Pollution, 2022)

The Paleogene to Neogene climate evolution and driving factors on the Qinghai-Tibetan Plateau - Jiagang Zhao; Shufeng Li; Alexander Farnsworth; Paul J. Valdes; Tammo Reichgelt; Linlin Chen; Zhekun Zhou; Tao Su (Science China Earth Sciences, 2022)

Salt sealing induced in situ N-doped porous carbon derived from wheat bran for the removal of doxycycline from aqueous solution - Linlin Liang; Xinyong Niu; Xiuli Han; Chun Chang; Junying Chen (Environmental Science and Pollution Research, 2022)

Deep-Sea-Derived Fungi as Valuable Producers of Cytotoxic Secondary Metabolites and Their Leads Potential - Guangrong Zhao; Wenli Tang; Jianlong Zhang; Peimin Shi; Youzhi Li; Jiao Wang; Qingqin Shen; Haixia Si; Linlin Jiang; Xin Yu; Hongwei Zhu; Guozhong Chen; et al. (Frontiers in Marine Science, 2022)
Cancer is the leading lethal disease worldwide. Natural products have contributed significantly to the development of approved therapeutic agents. Therefore, research into new bioactive naturally sourced metabolites with lead potential is urgently needed. It is well-known that marine microorganisms are by far one of the most notable and prolific sources of bioactive natural products. Among them, deep-sea-derived fungi are extraordinarily adapted and metabolically active under extreme environmental conditions, which enable them to produce a large number of novel secondary metabolites. Chemical examination of deep-sea-derived fungi has yielded enormous amounts of cytotoxic natural products and potential drug leads. This review summarizes a total of 229 cytotoxic compounds isolated from deep-sea-derived fungi from 2010 to 2021. The emphasis is on the unique chemical diversity of these metabolic products, together with their relevant cytotoxic properties. Among the isolated metabolites, 82 compounds have been found to possess moderate to potent cytotoxic activities. Meanwhile, we also highlight some compounds with potent cytotoxicities (namely “star molecules”) considering their high drug lead potential. This review reveals deep-sea-derived fungi as considerable resources for the development of new drugs and the potential of the newly discovered secondary metabolites as valuable antitumor lead compounds.

Correction to: Circular RNA hsa_circ_0000034 accelerates retinoblastoma advancement through the miR-361-3p/ADAM19 axis - Yanhua Jiang; Fan Xiao; Lin Wang; Ting Wang; Linlin Chen (Molecular and Cellular Biochemistry, 2022)

Traditional fermented soybean products: processing, flavor formation, nutritional and biological activities - Libo Liu; Xiaoqian Chen; Linlin Hao; Guofang Zhang; Zhao Jin; Chun Li; Yuzhuo Yang; Jiajia Rao; Bingcan Chen (Critical Reviews in Food Science and Nutrition, 2022)

Effects of Smooth Cordgrass Spartina alterniflora Invasion on Macrobenthic Fauna in the Yellow River Delta - Shaoyu Jiang; Chuanxin Zhang; Linlin Chen; Chunyun Liu; Lang Yan; Baoquan Li (Wetlands, 2022)

Deep convolutional neural network with random field model for lake ice mapping from Sentinel-1 imagery - Zhiguo Ma; Zihao Liu; Jiabin Pu; Linlin Xu; Kui Li; Linglong Wangqu; Rui Wu; Yiyi Ma; Ye Chen; Claude Duguay (International Journal of Remote Sensing, 2021)

Different Changing Patterns of Three NOS–NO System Activities after Ischemia–Reperfusion in Rabbit with AMI - Jun Zhang; Chao Chen; Fengpeng Li; Guangren Gao; Jinguo Fu; Heping Niu; Kai Yu; Lei Wang; Run Guo; Yanfang Wan; Zhanfeng Ma; Qianyu Zhang; et al. (Cell Biochemistry and Biophysics, 2021)

Late Eocene sclerophyllous oak from Markam Basin, Tibet, and its biogeographic implications - Linlin Chen; Weiyudong Deng; Tao Su; Shufeng Li; Zhekun Zhou (Science China Earth Sciences, 2021)

Large-Eddy Simulation of Cavitating Tip Leakage Vortex Structures and Dynamics around a NACA0009 Hydrofoil - Linlin Geng; Desheng Zhang; Jian Chen; Xavier Escaler (Journal of Marine Science and Engineering, 2021)
The tip leakage vortex (TLV) has aroused great concern for turbomachine performance, stability and noise generation as well as cavitation erosion. To better understand structures and dynamics of the TLV, large-eddy simulation (LES) is coupled with a homogeneous cavitation model to simulate the cavitation flow around a NACA0009 hydrofoil with a given clearance. The numerical results are validated by comparisons with experimental measurements. The results demonstrate that the present LES can well predict the mean behavior of the TLV. By visualizing the mean streamlines and mean streamwise vorticity, it shows that the TLV dominates the end-wall vortex structures, and that the generation and evolution of the other vortices are found to be closely related to the development of the TLV. In addition, as the TLV moves downstream, it undergoes an interesting progression, i.e., the vortex core radius keeps increasing and the axial velocity of vortex center experiences a conversion from jet-like profile to wake-like profile.

Estimation of the SARS-CoV-2 transmission probability in confined traffic space and evaluation of the mitigation strategies - Linlin Chen; Guangze Ban; Enshen Long; Gretchen Kalonji; Zhu Cheng; Li Zhang; Shurui Guo (Environmental Science and Pollution Research, 2021)

High-frequency in vitro plantlet regeneration in Lilium davidii var. unicolour Salisb, an important edible and medicinal plant, and confirmation of genetic fidelity of regeneration plantlets using ISSR markers - Linlin Yang; Liqin Chao; Xiuhong Su; Chunyan Wang; Chengming Dong; Suiqing Chen (Plant Biotechnology Reports, 2021)

Biochar Derived from Treated Lotus Stem and Adsorption of Phthalic Acid Esters - Ruiling Zhang; Linlin Chen; Binbin Qiu; Xiaojing Sun; Songyan Qin; Bo Wang; Feiyue Li; Lixin Zhao; Zhe Zhu (Water, Air, & Soil Pollution, 2021)

The behavioral and antioxidant response of the bivalve Gomphina veneriformis to sediment burial effect - Xiaojing Li; Linlin Chen; Zhengquan Zhou; Baoquan Li; Xin Liu (Acta Oceanologica Sinica, 2021)

A Role for Transmembrane Protein 16C/Slack Impairment in Excitatory Nociceptive Synaptic Plasticity in the Pathogenesis of Remifentanil-induced Hyperalgesia in Rats - Yize Li; Linlin Zhang; Jing Li; Chunyan Wang; Yi Chen; Yuan Yuan; Keliang Xie; Guolin Wang; Yonghao Yu (Neuroscience Bulletin, 2021)

miR-146a-3p suppressed the differentiation of hAMSCs into Schwann cells via inhibiting the expression of ERBB2 - Wei Chen; Linlin Ji; Zairong Wei; Chenglan Yang; Shusen Chang; Yucheng Zhang; Kaiyu Nie; Lingli Jiang; Yurong Deng (Cell and Tissue Research, 2021)
Human amniotic mesenchymal stem cells (hAMSCs) can be differentiated into Schwann-cell-like cells (SCLCs) in vitro. However, the underlying mechanism of cell differentiation remains unclear. In this study, we explored the phenotype and multipotency of hAMSCs, which were differentiated into SCLCs, and the expression of nerve repair-related Schwann markers, such as S100 calcium binding protein B (S-100), TNF receptor superfamily member 1B (P75), and glial fibrillary acidic protein (GFAP) were observed to be significantly increased. The secreted functional neurotrophic factors, like brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), and neurotrophin-3 (NT-3), were determined and also increased with the differentiation time. Moreover, miR-146a-3p, which significantly decreased during the differentiation of hAMSCs into SCLCs, was selected by miRNA-sequence analysis. Further molecular mechanism studies showed that Erb-B2 receptor tyrosine kinase 2 (ERBB2) was an effective target of miR-146a-3p and that miR-146a-3p down-regulated ERBB2 expression by binding to the 3′-UTR of ERBB2. The expression of miR-146a-3p markedly decreased, while the mRNA levels of ERBB2 increased with the differentiation time. The results showed that down-regulating miR-146a-3p could promote SC lineage differentiation and suggested that miR-146a-3p negatively regulated the Schwann-like phenotype differentiation of hAMSCs by targeting ERBB2. The results will be helpful to establish a deeper understanding of the underlying mechanisms and find novel strategies for cell therapy.

Development of the CSOMIO Coupled Ocean-Oil-Sediment- Biology Model - Dmitry S. Dukhovskoy; Steven L. Morey; Eric P. Chassignet; Xu Chen; Victoria J. Coles; Linlin Cui; Courtney K. Harris; Robert Hetland; Tian-Jian Hsu; Andrew J. Manning; Michael Stukel; Kristen Thyng; et al. (Frontiers in Marine Science, 2021)
The fate and dispersal of oil in the ocean is dependent upon ocean dynamics, as well as transformations resulting from the interaction with the microbial community and suspended particles. These interaction processes are parameterized in many models limiting their ability to accurately simulate the fate and dispersal of oil for subsurface oil spill events. This paper presents a coupled ocean-oil-biology-sediment modeling system developed by the Consortium for Simulation of Oil-Microbial Interactions in the Ocean (CSOMIO) project. A key objective of the CSOMIO project was to develop and evaluate a modeling framework for simulating oil in the marine environment, including its interaction with microbial food webs and sediments. The modeling system developed is based on the Coupled Ocean-Atmosphere-Wave-Sediment Transport model (COAWST). Central to CSOMIO’s coupled modeling system is an oil plume model coupled to the hydrodynamic model (Regional Ocean Modeling System, ROMS). The oil plume model is based on a Lagrangian approach that describes the oil plume dynamics including advection and diffusion of individual Lagrangian elements, each representing a cluster of oil droplets. The chemical composition of oil is described in terms of three classes of compounds: saturates, aromatics, and heavy oil (resins and asphaltenes). The oil plume model simulates the rise of oil droplets based on ambient ocean flow and density fields, as well as the density and size of the oil droplets. The oil model also includes surface evaporation and surface wind drift. A novel component of the CSOMIO model is two-way Lagrangian-Eulerian mapping of the oil characteristics. This mapping is necessary for implementing interactions between the ocean-oil module and the Eulerian sediment and biogeochemical modules. The sediment module is a modification of the Community Sediment Transport Modeling System. The module simulates formation of oil-particle aggregates in the water column. The biogeochemical module simulates microbial communities adapted to the local environment and to elevated concentrations of oil components in the water column. The sediment and biogeochemical modules both reduce water column oil components. This paper provides an overview of the CSOMIO coupled modeling system components and demonstrates the capabilities of the modeling system in the test experiments.

IL-21 enhances STAT3/Blimp-1 signaling pathway in B cells and contributes to plasma cell differentiation in newly diagnosed patients with myasthenia gravis - Yanan Xu; Xiaoyu Huang; Fengzhan Li; Tan Liu; Tingting Yang; Fei Chen; Jie Zhu; Meng Pan; Yong Zhang; Yuzhong Wang; Linlin Fu; Chenghua Xiao; et al. (Immunologic Research, 2021)

Circular RNA has_circ_0000034 accelerates retinoblastoma advancement through the miR-361-3p/ADAM19 axis - Yanhua Jiang; Fan Xiao; Lin Wang; Ting Wang; Linlin Chen (Molecular and Cellular Biochemistry, 2021)

Black Soldier Fly (Hermetia illucens) Larvae Significantly Change the Microbial Community in Chicken Manure - Xingxiao Zhang; Junzhe Zhang; Linlin Jiang; Xin Yu; Hongwei Zhu; Jianlong Zhang; Zhibin Feng; Xiang Zhang; Guozhong Chen; Zhijian Zhang (Current Microbiology, 2021)

Spatio-temporal variation of subtidal macrobenthic fauna and the ecological assessment of Longkou Artificial Island construction in Bohai Sea, China - Xiaojing Li; Linlin Chen; Zhengquan Zhou; Baoquan Li; Xin Liu; Lufei Yang; Bo Liu; Bo Song (Journal of Oceanology and Limnology, 2020)

Colloidal gold-based immunochromatographic strip assay for the rapid detection of diminazene in milk - Linlin Chen; Yaning Sun; Xiaofei Hu; Yunrui Xing; Sharon Kwee; Guanqiong Na; Gaiping Zhang (Food Additives & Contaminants: Part A, 2020)

Somatic mutations in planar cell polarity genes in neural tissue from human fetuses with neural tube defects - Tian Tian; Yunping Lei; Yongyan Chen; Menuka Karki; Lei Jin; Richard H. Finnell; Linlin Wang; Aiguo Ren (Human Genetics, 2020)

Resilience-based retrofitting of existing urban RC-frame buildings using seismic isolation - Cantian Yang; Linlin Xie; Aiqun Li; Demin Zeng; Junbo Jia; Xi Chen; Min Chen (Earthquake Engineering and Engineering Vibration, 2020)

Review on observational studies of western tropical Pacific Ocean circulation and climate - Dunxin Hu; Fan Wang; Janet Sprintall; Lixin Wu; Stephen Riser; Sophie Cravatte; Arnold Gordon; Linlin Zhang; Dake Chen; Hui Zhou; Kentaro Ando; Jianing Wang; et al. (Journal of Oceanology and Limnology, 2020)

Comparison of different soil dielectric models for microwave soil moisture retrievals - Linlin Zhang; Qingyan Meng; Die Hu; Ying Zhang; Shun Yao; Xu Chen (International Journal of Remote Sensing, 2020)

The interface mechanical properties and breakage analysis of the flexible isolation layer under ore drawing from a single funnel - Qingfa Chen; Linlin Meng; Shikang Qin; Qinglin Chen (Arabian Journal of Geosciences, 2020)

Low shear stress damages endothelial function through STAT1 in endothelial cells (ECs) - Linlin Zhu; Feng Wang; Hongfeng Yang; Junjie Zhang; Shaoliang Chen (Journal of Physiology and Biochemistry, 2020)

Identification of Fusarium graminearum-responsive miRNAs and their targets in wheat by sRNA sequencing and degradome analysis - Xiaojie Jin; Linlin Jia; Yongxia Wang; Baoquan Li; Dongfa Sun; Xueyan Chen (Functional & Integrative Genomics, 2020)

Wheat methionine sulfoxide reductase A4.1 interacts with heme oxygenase 1 to enhance seedling tolerance to salinity or drought stress - Pengcheng Ding; Linlin Fang; Guangling Wang; Xiang Li; Shu Huang; Yankun Gao; Jiantang Zhu; Langtao Xiao; Jianhua Tong; Fanguo Chen; Guangmin Xia (Plant Molecular Biology, 2019)

Exploration of the key functional strains from an azo dye degradation microbial community by DGGE and high-throughput sequencing technology - Yan Chen; Lizhen Zhang; Linlin Feng; Guotao Chen; Yuanxiu Wang; Zhijun Zhai; Qinghua Zhang (Environmental Science and Pollution Research, 2019)

Effects of key species mud snail Bullacta exarata (Gastropoda) on oxygen and nutrient fluxes at the sediment-water interface in the Huanghe River Delta, China - Baoquan Li; Tjeerd J. Bouma; Quanchao Wang; Laura M. Soissons; Francesco Cozzoli; Guanghai Feng; Xiaojing Li; Zhengquan Zhou; Linlin Chen (Acta Oceanologica Sinica, 2019)

Diversity of the Fusarium pathogens associated with crown rot in the Huanghuai wheat‐growing region of China - Haifeng Zhou; Xiaolun He; Shuo Wang; Qingzhou Ma; Bingjian Sun; Shengli Ding; Linlin Chen; Meng Zhang; Honglian Li (Environmental Microbiology, 2019)
Summary To investigate the distribution and diversity of the pathogens associated with Fusarium crown rot in the Huanghuai wheat‐growing region (HHWGR) of China, we collected wheat samples with symptomatic stem bases from seven provinces in the HHWGR between 2013 and 2016. A total of 1196 isolates obtained from 222 locations were identified as 9 Fusarium species based on morphological and molecular identification. Of these pathogen species, F. pseudograminearum was the dominant species. Furthermore, F. sinensis was isolated from the disease specimens and tested for virulence to wheat. The result of the pathogenicity revealed that an intraspecific differentiation existed in F. pseudograminearum ; sequence analysis of the EF‐1α gene showed that 194 F. pseudograminearum isolates were differentiated into two distinct clades which closed to the strains from Australia and China respectively, but neither pathogenicity nor EF‐1α sequence was related to the geographic origins of these isolates. However, universal rice primers‐polymerase chain reaction showed a correlation with the geographical origins of the 194 isolates, which were divided into eight subclusters, the level of genetic diversity was higher within a geographical population than among the different populations. The results of these analyses can be directly used to facilitate disease monitoring and development of control strategies.

Ozonation catalyzed by iron- and/or manganese-supported granular activated carbons for the treatment of phenol - Wei Xiong; Nan Chen; Chuanping Feng; Yang Liu; Ningping Ma; Jian Deng; Linlin Xing; Yu Gao (Environmental Science and Pollution Research, 2019)

Major ion and dissolved heavy metal geochemistry, distribution, and relationship in the overlying water of Dongting Lake, China - Yan Chen; Lingqing Wang; Tao Liang; Jun Xiao; Jing Li; Haicheng Wei; Linlin Dong (Environmental Geochemistry and Health, 2019)

A study of the coupled bioelectrochemical system-upflow anaerobic sludge blanket for efficient transformation of 2,4-dichloronitrobenzene - Hui Chen; Donghui Lu; Linlin Chen; Caiqin Wang; Xiangyang Xu; Liang Zhu (Environmental Science and Pollution Research, 2019)

Sodium Fluoride (NaF) Induces Inflammatory Responses Via Activating MAPKs/NF-κB Signaling Pathway and Reducing Anti-inflammatory Cytokine Expression in the Mouse Liver - Linlin Chen; Ping Kuang; Huan Liu; Qin Wei; Hengmin Cui; Jing Fang; Zhicai Zuo; Junliang Deng; Yinglun Li; Xun Wang; Ling Zhao (Biological Trace Element Research, 2019)

Plastic Mulch and Plant Density Influencing Soil Water Content and Yield of Rainfed Maize in North‐Eastern China - Shijun Sun; Zhijun Chen; Hao Jiang; Xudong Zhang; Linlin Zhang; Daocai Chi (Irrigation and Drainage, 2019)
Plastic mulch, in combination with high plant density, is a common practice for rainfed maize production in north‐eastern China. However, the influence of these practices on soil water storage, maize yield and maize water productivity in different precipitation years is not well understood. In this paper, a 3‐year split‐plot field experiment was designed to compare non‐mulching and plastic film mulching in maize at 67 500 and 82 500 plants per ha in 2013, 2014 and 2015, and also 97 500 plants per ha in 2014 and 2015. Results revealed an increasing trend of precipitation in the study area from 1962 to 2015 and that the number of dry years and extreme years (including extreme dry and wet years) was increasing. In the moderately wet year 2013 and the moderately dry year 2015, the combination of 82 500 plants per ha and plastic film mulching produced the highest yield and water productivity (8.2 t ha −1 , 1.7 kg m −3 and 8.3 t ha −1 , 2.3 kg m −3 , respectively) for maize, while in the extremely dry year 2014 the highest yield (5.6 t ha −1 ) occurred with 97 500 plants per ha and non‐mulching. This research might be helpful for smallholder farmers needing optimal agricultural strategies to improve maize production in rainfed areas of north‐east China. © 2018 John Wiley & Sons, Ltd.

MiR-449a-5p mediates mitochondrial dysfunction and phenotypic transition by targeting Myc in pulmonary arterial smooth muscle cells - Chen Zhang; Cui Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Mingfei Ma; Xiaodong Zheng; Min Mao; Tingting Shen; Daling Zhu (Journal of Molecular Medicine, 2019)

Identification of protein arginine methyltransferase 7 (PRMT7) inhibitor by virtual screening and biological evaluation in vitro - Linlin Liu; Xiaoning Kai; Qingqing Chen; Ling Zhang; Ruosi Yao; Jian Gao (Medicinal Chemistry Research, 2019)

A novel long non-coding RNA, lncKBTBD10, involved in bovine skeletal muscle myogenesis - Mingming Chen; Xin Li; Xiaojuan Zhang; Yan Li; Junxing Zhang; Minhui Liu; Linlin Zhang; Xiangbin Ding; Xinfeng Liu; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2019)

Tissue Distribution and Gender-Specific Protein Expression of Cytochrome P450 in five Mouse Genotypes with a Background of FVB - Jiamei M. Chen; Qisong S. Zhang; Xiaoyan Y. Li; Xia Gong; Yanjiao J. Ruan; Sijing J. Zeng; Linlin L. Lu; Xiaoxiao X. Qi; Ying Wang; Ming Hu; Lijun J. Zhu; Zhongqiu Q. Liu (Pharmaceutical Research, 2018)

Size distribution of individuals in the population of Asterias amurensis (Echinodermata: Asteroidea) and its reproductive cycle in China - Baoquan Li; Zhengquan Zhou; Bingjun Li; Quanchao Wang; Xiaojing Li; Linlin Chen (Acta Oceanologica Sinica, 2018)

Synaptobrevin-2 facilitates the trafficking and function of atrial SK2 channel - Tao Li; Xuehui Fan; Yiyan Yu; Linlin Chen; Wenjun Huang; Yan Yang; Jimin Cao; Xiaorong Zeng; Xiaoqiu Tan (Science China Life Sciences, 2018)

Adsorptive removal of organics from aqueous phase by acid-activated coal fly ash: preparation, adsorption, and Fenton regenerative valorization of “spent” adsorbent - Nannan Wang; Linlin Hao; Jiaqing Chen; Qiang Zhao; Han Xu (Environmental Science and Pollution Research, 2018)

Macrobenthic assemblage characteristics under stressed waters and ecological health assessment using AMBI and M-AMBI: a case study at the Xin’an River Estuary, Yantai, China - Zhengquan Zhou; Xiaojing Li; Linlin Chen; Baoquan Li; Tiantian Liu; Binghua Ai; Lufei Yang; Bo Liu; Qiao Chen (Acta Oceanologica Sinica, 2018)

Labile organic carbon fractions and carbon pool management index in a 3-year field study with biochar amendment - Xu Yang; Di Wang; Yu Lan; Jun Meng; Linlin Jiang; Qiang Sun; Dianyun Cao; Yuanyuan Sun; Wenfu Chen (Journal of Soils and Sediments, 2018)

5-Azacytidine treatment and TaPBF-D over-expression increases glutenin accumulation within the wheat grain by hypomethylating the Glu-1 promoters - Jiantang Zhu; Linlin Fang; Jiaqi Yu; Ying Zhao; Fanguo Chen; Guangmin Xia (Theoretical and Applied Genetics, 2018)

The role of Ustilaginoidea virens sclerotia in increasing incidence of rice false smut disease in the subtropical zone in China - Mingli Yong; Qide Deng; Linlin Fan; Jiankun Miao; Chaohui Lai; Hongming Chen; Xiujuan Yang; Shu Wang; Furu Chen; Li Jin; Binghui Yang; Yuanjun Bai; et al. (European Journal of Plant Pathology, 2018)

Plantactinospora solaniradicis sp. nov., a novel actinomycete isolated from the root of a tomato plant (Solanum lycopersicum L.) - Wenchao Li; Xiaowei Guo; Linlin Shi; Junwei Zhao; Liangliang Yan; Xiaotong Zhong; Chen Zhang; Yufei Chen; Xiangjing Wang; Wensheng Xiang (Antonie van Leeuwenhoek, 2018)

MicroRNA-192 regulates hypertrophic scar fibrosis by targeting SIP1 - Yan Li; Julei Zhang; Wei Zhang; Yang Liu; Yuehua Li; Kejia Wang; Yijie Zhang; Chen Yang; Xiaoqiang Li; Jihong Shi; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Integrated space geodesy for mapping land deformation over Choushui River Fluvial Plain, Taiwan - Linlin Ge; Alex Hay-Man Ng; Zheyuan Du; Horng-Yue Chen; Xiaojing Li (International Journal of Remote Sensing, 2017)

MiR-125a regulates mitochondrial homeostasis through targeting mitofusin 1 to control hypoxic pulmonary vascular remodeling - Cui Ma; Chen Zhang; Mingfei Ma; Lixin Zhang; Linlin Zhang; Fengying Zhang; Yingli Chen; Fangyuan Cao; Minghui Li; Guangtian Wang; Tingting Shen; Hongmin Yao; et al. (Journal of Molecular Medicine, 2017)

A lncRNA promotes myoblast proliferation by up-regulating GH1 - Yingwei Yue; Congfei Jin; Mingming Chen; Linlin Zhang; Xinfeng Liu; Wenzhi Ma; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Disposition of Flavonoids for Personal Intake - Shuqiang Liu; Haihui Zheng; Rongjin Sun; Huangyu Jiang; Jiamei Chen; Jia Yu; Qisong Zhang; Qingwei Chen; Lijun Zhu; Ming Hu; Linlin Lu; Zhongqiu Liu (Current Pharmacology Reports, 2017)

miR-155 promotes cutaneous wound healing through enhanced keratinocytes migration by MMP-2 - Longlong Yang; Zhao Zheng; Qin Zhou; Xiaozhi Bai; Lei Fan; Chen Yang; Linlin Su; Dahai Hu (Journal of Molecular Histology, 2017)

Late Quaternary lake evolution in the Gaxun Nur basin, central Gobi Desert, China, based on quartz OSL and K‐feldspar pIRIR dating of paleoshorelines - Guoqiang Li; Fangliang Li; Ming Jin; Linlin She; Yanwu Duan; David Madsen; Leibin Wang; Fahu Chen (Journal of Quaternary Science, 2017)
Paleoenvironmental changes in the Gobi Desert of Mongolia are of global significance because fluvial and lacustrine deposits in the region constitute one of the dominant sources of Northern Hemisphere dust. A series of well‐preserved geomorphic shoreline features at different elevations around the Gaxun Nur basin, central Gobi Desert, indicate past fluctuations of the basin's terminal lake. We measured the exact elevation of shorelines in the basin using a Differential Global Positioning System, and found six shorelines at ∼24, ∼20, ∼18, ∼16, ∼15 m and ∼8 m above the modern basin floor. Quartz optically stimulated luminescence and K‐feldspar post‐infrared infrared stimulated luminescence methods were used to date these shoreline features. The reliability of the dates was confirmed using internal checks of luminescence characteristics and by comparing the quartz and K‐feldspar ages. Our results suggest a lake developed in the Gaxun Nur basin by at least ∼121 ka. Lake levels increased from ∼8 to ∼24 m from ∼121 to ∼85 ka. A 20–13‐m‐deep lake again formed in the basin between ∼8.4 and 0.8 ka. Monsoonal precipitation and temperature variations during Marine Isotope Stage 5 and the mid–late Holocene were the likely causes of paleolake formation and lake level fluctuations.

Effects of maize stover and its derived biochar on greenhouse gases emissions and C-budget of brown earth in Northeast China - Xu Yang; Yu Lan; Jun Meng; Wenfu Chen; Yuwei Huang; Xiaoyi Cheng; Tianyi He; Ting Cao; Zunqi Liu; Linlin Jiang; Jiping Gao (Environmental Science and Pollution Research, 2017)

Gelatin microspheres containing calcitonin gene-related peptide or substance P repair bone defects in osteoporotic rabbits - Jianghao Chen; Wei Liu; Jinxiu Zhao; Cong Sun; Jie Chen; Kaijin Hu; Linlin Zhang; Yuxiang Ding (Biotechnology Letters, 2017)

Estimate of Boundary-Layer Depth Over Beijing, China, Using Doppler Lidar Data During SURF-2015 - Meng Huang; Zhiqiu Gao; Shiguang Miao; Fei Chen; Margaret A. LeMone; Ju Li; Fei Hu; Linlin Wang (Boundary-Layer Meteorology, 2017)

Effect of LA on the Growth and Development of the Main Organs in Female Mice - Xiuyuan He; Feng Lin; Yongtao Li; Yuxia Chen; Jing Li; Linlin Guo; Xuelei Han; Huan Song (Biological Trace Element Research, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Identification of forty-five gene-derived polymorphic microsatellite loci for the sea cucumber, Apostichopus japonicus - MENG CHEN; LINLIN GAO; WEIJIE ZHANG; HONGZHENG YOU; QIAN SUN; YAQING CHANG (Journal of Genetics, 2016)

Phosphatidylinositol 3-phosphate, an essential lipid in Phytophthora sojae, enriches in the haustoria during infection - Linlin Chen; Wen Wang; Ying Hou; Yuren Wu; Honglian Li; Daolong Dou (Australasian Plant Pathology, 2016)

Reactive oxygen species effect PASMCs apoptosis via regulation of dynamin-related protein 1 in hypoxic pulmonary hypertension - Lixin Zhang; Cui Ma; Chen Zhang; Mingfei Ma; Fengying Zhang; Linlin Zhang; Yingli Chen; Fangyuan Cao; Shuzhen Li; Daling Zhu (Histochemistry and Cell Biology, 2016)

Spatial and Seasonal Variations of Polycyclic Aromatic Hydrocarbons (PAHs) in Ambient Particulate Matter (PM10, PM2.5) in Three Mega-Cities in China and Identification of Major Contributing Source Types - Linlin Zhang; Rui Chen; Jungang Lv (Bulletin of Environmental Contamination and Toxicology, 2016)

CspE is Overproduced by Temperature Downshift in the Acinetobacter johnsonii DBP-3 - Dan Su; Linlin Hao; Fuwang Chen; Siming Li; Ahmed Mohamed Abdelrahman; Yu Zhang; Hao Yu; Songcai Liu; Mingtang Li (Current Microbiology, 2016)

Expression of HIV-encoded microRNA-TAR and its inhibitory effect on viral replication in human primary macrophages - Li Li; Haimin Feng; Qin Da; Honglin Jiang; Lang Chen; Linlin Xie; Qiuling Huang; Hairong Xiong; Fan Luo; Lei Kang; Yan Zeng; Haitao Hu; et al. (Archives of Virology, 2016)

Structural controls on joint development in the southeastern margin of the Ordos basin - Linlin Wang; Bo Jiang; Jilin Wang; Zhenghui Qu; Run Chen (Arabian Journal of Geosciences, 2016)

NF45 overexpression is associated with poor prognosis and enhanced cell proliferation of pancreatic ductal adenocarcinoma - Chunhua Wan; Chen Gong; Li Ji; Xiaorong Liu; Yayun Wang; Liang Wang; Mengting Shao; Linlin Yang; Shaoqing Fan; Yin Xiao; Xiaotong Wang; Manhua Li; et al. (Molecular and Cellular Biochemistry, 2015)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

Millennium tree-ring reconstruction of drought variability in the eastern Qilian Mountains, northwest China - Xiaohua Gou; Yang Deng; Linlin Gao; Fahu Chen; Edward Cook; Meixue Yang; Fen Zhang (Climate Dynamics, 2015)

Seasonal and interannual variations of carbon exchange over a rice-wheat rotation system on the North China Plain - Chen Chen; Dan Li; Zhiqiu Gao; Jianwu Tang; Xiaofeng Guo; Linlin Wang; Bingcheng Wan (Advances in Atmospheric Sciences, 2015)

An 850‐year tree‐ring‐based reconstruction of drought history in the western Qilian Mountains of northwestern China - Xiaohua Gou; Linlin Gao; Yang Deng; Fahu Chen; Meixue Yang; Christopher Still (International Journal of Climatology, 2015)
Studies of regional drought history will be helpful for understanding current hydroclimate variability with global warming as well as predicting future hydroclimate shifts. Long‐term tree‐ring records are scarce in the western Qilian Mountains of northwestern China, which is also the western boundary of the natural distribution of Qilian Juniper ( Juniperus przewalskii Kom.) in this area. Here, we present an 850‐year ( AD 1161 –2010) reconstruction of May–July self‐calibrating Palmer Drought Severity Index ( scPDSI ) in the western Qilian Mountains that is based on two nearly millennia of ring‐width chronologies derived from long‐lived Qilian Juniper trees. The reconstruction suggests a relatively dry phase from the 15th century to the 18th century during the Little Ice Age ( LIA ) and a relatively wet period over the past two centuries. This reconstruction is consistent with other tree‐ring‐based hydroclimatic reconstructions from the northeastern Tibetan Plateau, as well as the corresponding century‐scale solar activity during the LIA . The three mega‐drought periods ( AD 1260s –1340s, 1430s–1540s and 1640s–1740s) recorded by the tree‐ring series also correspond to the Wolf, Spörer and Maunder solar activity minimum periods. Results of the multi‐tape method analysis and wavelet analysis further confirmed the relationship between regional hydroclimate variability and solar activity forcing.

Pygo2 siRNA Inhibit the Growth and Increase Apoptosis of U251 Cell by Suppressing Histone H3K4 Trimethylation - Mingcong Li; Linlin Chao; Jian Wu; Hao Xu; Shanghan Shen; Sifang Chen; Xin Gao; Ning Yu; Zhanxiang Wang (Journal of Molecular Neuroscience, 2015)

Stromal cell-derived factor 1 (SDF-1) accelerated skin wound healing by promoting the migration and proliferation of epidermal stem cells - Rui Guo; Linlin Chai; Liang Chen; Wenguang Chen; Liangpeng Ge; Xiaoge Li; Hongli Li; Shirong Li; Chuan Cao (In Vitro Cellular & Developmental Biology - Animal, 2015)

Roles of oxidative stress and endoplasmic reticulum stress in selenium deficiency-induced apoptosis in chicken liver - Linlin Yao; Qiang Du; Haidong Yao; Xi Chen; Ziwei Zhang; Shiwen Xu (BioMetals, 2015)

Identification and characteristics of imipenem-resistant Acinetobacter baumannii in surgical wards in a Chinese university hospital - Dalin Wang; Linlin Ma; Zhenyu Wu; Mingcheng Li; Xiaohan Li; Wei Zhang; Kun Chen (Infectious Diseases, 2015)

Erratum to: Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Effect of volatile organic compounds absorbed to fresh biochar on survival of Bacillus mucilaginosus and structure of soil microbial communities - Daquan Sun; Jun Meng; Hao Liang; E. Yang; Yuwei Huang; Wenfu Chen; Linlin Jiang; Yu Lan; Weiming Zhang; Jiping Gao (Journal of Soils and Sediments, 2015)

Selenium Deficiency Influences the Gene Expressions of Heat Shock Proteins and Nitric Oxide Levels in Neutrophils of Broilers - Xi Chen; Haidong Yao; Linlin Yao; Jinxin Zhao; Yilin Luan; Ziwei Zhang; Shiwen Xu (Biological Trace Element Research, 2014)

Oxidative stress promotes d-GalN/LPS-induced acute hepatotoxicity by increasing glycogen synthase kinase 3β activity - Linlin Wei; Feng Ren; Xiangying Zhang; Tao Wen; Hongbo Shi; Sujun Zheng; Jing Zhang; Yu Chen; Yuanping Han; Zhongping Duan (Inflammation Research, 2014)

Organochlorine pesticide contamination in marine organisms of Yantai coast, northern Yellow Sea of China - Jing Chen; Linlin Chen; Dongyan Liu; Gaosheng Zhang (Environmental Monitoring and Assessment, 2014)

Identification of Novel MicroRNA Signatures Linked to Experimental Autoimmune Myasthenia Gravis Pathogenesis: Down-Regulated miR-145 Promotes Pathogenetic Th17 Cell Response - Jiao Wang; Shuangshuang Zheng; Ning Xin; Changxin Dou; Linlin Fu; Xiuying Zhang; Jing Chen; Yanyan Zhang; Deqin Geng; Chenghua Xiao; Guiyun Cui; Xia Shen; et al. (Journal of Neuroimmune Pharmacology, 2013)

Investigation and integrated molecular diagnosis of root-knot nematodes in Panax notoginseng root in the field - Linlin Dong; Hui Yao; Qiushi Li; Jingyuan Song; Ying Li; Hongmei Luo; Shilin Chen (European Journal of Plant Pathology, 2013)

Rhizobacteria (Pseudomonas sp. SB) assist phytoremediation of oily-sludge-contaminated soil by tall fescue (Testuca arundinacea L.) - Wuxing Liu; Jianying Sun; Linlin Ding; Yongming Luo; Mengfang Chen; Caixian Tang (Plant and Soil, 2013)

Polybrominated Diphenyl Ethers Contamination in Marine Organisms of Yantai Coast, Northern Yellow Sea of China - Jing Chen; Linlin Chen; Dongyan Liu; Gaosheng Zhang (Bulletin of Environmental Contamination and Toxicology, 2013)

Expansivity and compressibility of wadeite-type K2Si4O9 determined by in situ high T/P experiments, and their implication - Linlin Chang; Zhiqiang Chen; Xi Liu; Hejing Wang (Physics and Chemistry of Minerals, 2013)

Heavy metal contamination in the marine organisms in Yantai coast, northern Yellow Sea of China - Gaosheng Zhang; Dongyan Liu; Huifeng Wu; Linlin Chen; Qingxi Han (Ecotoxicology, 2012)

PTEN inhibits proliferation and functions of hypertrophic scar fibroblasts - Liang Guo; Liang Chen; Sheng Bi; Linlin Chai; Zengxiang Wang; Chuan Cao; Ling Tao; Shirong Li (Molecular and Cellular Biochemistry, 2012)

Expression of hGM-CSF in silk glands of transgenic silkworms using gene targeting vector - Renyu Xue; Huimei Chen; Linlin Cui; Guangli Cao; Wenlin Zhou; Xiaojian Zheng; Chengliang Gong (Transgenic Research, 2012)

Evaled Expression of ICAM-1 and Its Ligands in the Rat Spinal Cord Following Lipopolysaccharide Intraspinal Injection - Junling Yang; Min Fei; Yangyang Gu; Linlin Sun; Zhiyun Ben; Dan Zhou; Jianping Chen; Youhua Wang; Ping Wang; Aiguo Shen; Chun Cheng (NeuroMolecular Medicine, 2008)

Lipopolysaccharide induces expression of SSeCKS in rat lung microvascular endothelial cell - Chun Cheng; Haiou Liu; Haiyan Ge; Ji Qian; Jing Qin; Linlin Sun; Menling Chen; Meijuan Yan; Aiguo Shen (Molecular and Cellular Biochemistry, 2007)